Vinyl alcohol polymers and uses thereof

By polymerizing and saponifying the vinyl ester monomer from plants and the vinyl ester monomer from petroleum, a vinyl alcohol-based polymer with excellent properties was prepared, which solved the difficulty in saving petroleum resources and inhibition in the prior art. The issue of carbon dioxide emissions has achieved a production process of saving oil resources and environmentally friendly.

CN116034150BActive Publication Date: 2025-02-25KURARAY CO LTD
View PDF 32 Cites 0 Cited by

Patent Information

Application Number
CN202180056034.0
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2021-05-12
Filing Date
2021-08-11
Publication Date
2025-02-25
Estimated Expiration
2041-08-11

AI Technical Summary

Technical Problem

The prior art is difficult to provide vinyl alcohol-based polymers with the same or more properties as vinyl alcohol-based polymers derived from petroleum only, and it is difficult to save petroleum resources and inhibit carbon dioxide during the manufacturing process when using these polymers. emission.

Method used

A vinyl alcohol-based polymer with excellent properties was prepared by partially using vinyl ester monomers derived from plants and polymerizing and saponifying them with vinyl ester monomers derived from petroleum.

Benefits of technology

A vinyl alcohol-based polymer with the same or more properties as that of vinyl alcohol-based polymers derived from petroleum only is provided, thereby achieving conservation of petroleum resources and inhibition of carbon dioxide emissions during manufacturing.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure GDA0005172022960000521
    Figure GDA0005172022960000521
  • Figure GDA0005172022960000551
    Figure GDA0005172022960000551
  • Figure GDA0005172022960000571
    Figure GDA0005172022960000571
Patent Text Reader

Abstract

The present invention provides a vinyl alcohol polymer having equivalent properties to a vinyl alcohol polymer derived solely from petroleum, and when a vinyl alcohol polymer (PVA) is used, petroleum resources are saved and carbon dioxide emissions during the manufacturing process are suppressed. The present invention relates to a vinyl alcohol polymer (X), which is a vinyl alcohol polymer (X) obtained by polymerizing and saponifying a vinyl ester monomer (A) derived from a plant and a vinyl ester monomer (B) derived from petroleum, wherein the molar ratio of (A) / (B) is 5 / 95 to 100 / 0.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a vinyl alcohol polymer obtained by polymerizing and saponifying vinyl acetate synthesized from a plant-derived raw material such as biomass, a slurry additive, a drilling mud, a cement slurry, a filler for underground treatment, a multilayer structure having excellent oxygen barrier properties, a production method thereof, and a packaging material, a paper coating agent, a coated paper, a seed coating composition, an aqueous emulsion, an adhesive, a dispersion stabilizer for suspension polymerization of a vinyl compound, and a dispersion stabilization auxiliary for suspension polymerization of a vinyl compound comprising the same. Background Art

[0002] Vinyl alcohol polymers (hereinafter sometimes referred to as PVA) obtained by polymerizing and saponifying vinyl acetate are one of the few crystalline water-soluble polymers that have excellent interface properties and strength properties. Therefore, in addition to being used as stabilizers for paper processing, fiber processing and emulsions, they also occupy an important position as PVA films and PVA fibers.

[0003] Ethylene and acetic acid, which are raw materials of vinyl acetate, are produced from petroleum or natural gas, which are fossil resources. Specifically, ethylene is produced by mixing hydrocarbons, mainly naphtha, with water vapor, and thermally decomposing them, and then separating the products by distillation. In addition, acetic acid is produced by carbonylation reaction of methanol obtained by reacting carbon monoxide produced by partial oxidation of natural gas with hydrogen.

[0004] There is a risk of depletion of this fossil resource, and there are also concerns that the carbon dioxide emitted during the manufacturing process will accelerate global warming.

[0005] Furthermore, in mines and the like for collecting buried materials such as oil and natural gas, slurries for civil engineering and construction, represented by drilling slurries, have been conventionally used.

[0006] Drilling mud plays the role of, for example, transporting drilled rock pieces, drilling debris, etc., improving the lubricity of drill bits or drill pipes, burying holes in porous foundations, and offsetting the reservoir pressure (pressure from igneous rocks) generated by hydrostatic pressure. The drilling mud usually has water and bentonite as the main components, and achieves the target performance by further adding barite, salt, clay, etc. This drilling mud is required to have temperature stability and appropriate flow characteristics that are not significantly affected by changes in the concentration of electrolytes (such as carboxylates) in the foundation. In order to meet this requirement, it is necessary to adjust the viscosity of the drilling mud and inhibit the escape of water contained in the drilling mud (hereinafter sometimes referred to as "dehydration"). In order to adjust the viscosity of the drilling mud and inhibit dehydration, a method of adding polymers, such as starch, starch ether (carboxymethyl starch, etc.), carboxymethyl cellulose, carboxymethyl hydroxyethyl cellulose, etc. is usually adopted.

[0007] However, the addition of these polymers sometimes causes the viscosity of the drilling mud to increase extremely, making it difficult to inject the drilling mud using a pump. In addition, there are the following problems: starch and its derivatives do not fully inhibit dehydration in the temperature range exceeding about 120°C, and carboxymethyl cellulose and carboxymethyl hydroxyethyl cellulose do not fully inhibit dehydration in the temperature range of 140°C to 150°C.

[0008] On the other hand, drilling slurry is injected into the tubular space between the formation and the casing installed in the mine and solidified to fix the casing in the mine, protect the inner wall of the mine, etc. In general, the drilling slurry is injected into the tubular space using a pump. Therefore, in order to easily inject the drilling slurry using a pump, the drilling slurry is required to have an extremely low viscosity and not separate.

[0009] However, during cement grouting in a mine, material separation sometimes occurs, and moisture escapes into cracks in the mine, causing defects in the cement grouting portion. Therefore, dehydration reducing agents such as walnut shells, cotton seeds, clay minerals, and polymer compounds are added to drilling cement slurry, and vinyl alcohol polymers are well-known dehydration reducing agents.

[0010] Regarding the dehydration reducing agent for the vinyl alcohol polymer, for example, Patent Document 1 discloses a method using PVA having a saponification degree of 95 mol % or more.

[0011] Patent Document 2 discloses a method using PVA having a saponification degree of 92 mol % or less.

[0012] Patent Document 3 discloses a method using PVA having a saponification degree of 99 mol % or more.

[0013] When recovering oil or other underground resources from underground natural resource layers, the low recovery rate of these resources becomes a problem, and various methods are used to improve it. As a representative method, there is a method of injecting fluid into the underground oil field layer for replacement. As the fluid, salt water, clean water, polymer aqueous solution, steam, etc. are used, among which polymer aqueous solution is useful.

[0014] As an example, a method of injecting steam into an underground shale (mudstone) layer to cause cracks is widely used. In this method, a vertical hole (vertical mine) several thousand meters deep is first drilled vertically underground using a drill bit, and when the shale layer is reached, a horizontal hole (horizontal mine) with a diameter of ten to several dozen centimeters is drilled horizontally. Then, a polymer aqueous solution is pressed into the vertical mine and the horizontal mine to generate cracks (cracks) in the mine, and natural gas, oil (shale gas / oil), etc. flowing out of the cracks are recovered.

[0015] At this time, in order to make the already generated cracks grow larger or generate more cracks, underground processing fillers (additives) are sometimes used to temporarily seal a part of the already generated cracks, and in this state, the fracturing fluid filled into the mine is pressurized, so that the fluid gradually penetrates into other cracks, which can make the existing cracks grow significantly or generate new cracks.

[0016] As described above, underground treatment fillers (also called guide agents) are used to temporarily seal cracks. Therefore, sometimes used are materials that can maintain their shape for a certain period of time while sealing cracks, and then disappear or be dissolved and removed by hydrolysis when natural gas, oil, etc. are collected.

[0017] For example, there is an example of using PVA as a filler for underground treatment, and Patent Document 2 discloses a guide agent containing PVA.

[0018] In addition, Patent Document 3 discloses a guiding agent containing resin particles of PVA having a specific particle size.

[0019] Patent Document 4 discloses a filler for underground treatment containing PVA having a swelling ratio within a specific range after being immersed in water at a temperature of 80° C. for 30 minutes.

[0020] Multilayer structures with excellent oxygen barrier properties are used as packaging materials, etc. Aluminum foil is used as an intermediate layer of such multilayer structures because of its excellent oxygen barrier properties. However, there are problems such as residues generated when a multilayer structure including aluminum foil is incinerated, and the contents cannot be seen when the multilayer structure is used as a packaging material, and the contents cannot be checked with a metal detector.

[0021] Polyvinylidene chloride (hereinafter sometimes abbreviated as "PVDC") is not easy to absorb moisture and has good oxygen barrier properties even at high humidity. Therefore, multilayer structures formed by coating polyvinylidene chloride on various substrates are used as packaging materials, etc. As the aforementioned substrate, films such as biaxially stretched polypropylene (hereinafter sometimes abbreviated as "OPP"), biaxially stretched nylon (hereinafter sometimes abbreviated as "ON"), biaxially stretched polyethylene terephthalate (hereinafter sometimes abbreviated as "OPET"), and cellophane are used. However, there is a problem that if waste of multilayer structures containing PVDC is incinerated, hydrogen chloride gas will be generated.

[0022] For example, Patent Document 5 describes a film made of PVA containing 3 to 19 mol % of α-olefin units having 4 or less carbon atoms, and describes that the film has excellent water resistance and excellent oxygen barrier properties even under high humidity.

[0023] In addition, it is known that PVA can be applied to paper to enhance the strength of the paper, impart water resistance, oil resistance, gas barrier properties, etc., and is widely used. In addition, vinyl alcohol polymers are used as inorganic binders or dispersion stabilizers, and are also used as auxiliary agents for imparting functions to paper. For example, an example of using PVA as a paper coating agent is disclosed in Patent Document 6.

[0024] Seed treatment refers to the application of materials to seeds for the purpose of improving handleability, protecting seeds prior to germination, or supporting the germination process. Seed treatments, in turn, impart pest resistance properties to the seed or resulting plant by combining active "pesticide" ingredients such as insecticides, fungicides, and nematicides. Additionally, plant growth regulators may be added to the seed coating compound to improve seed treatment properties. Seed treatments eliminate or at least reduce the need for traditional foliar sprays of fungicides or insecticides.

[0025] Unfortunately, many known seed treatments are known to generate excessive dust during storage and application of seed material, which can result in the aggregation of large seed clumps, which can reduce germination efficiency.

[0026] For example, Patent Documents 7 to 20 disclose various and multiple seed coating compositions and ingredients for improving the handling, germination, storage and growth characteristics of seeds.

[0027] Typically, an aqueous seed coating composition comprises an aqueous medium, one or more functional additives and a binder that forms a matrix for the various functional additives when dried after application, and a protective film for covering the seeds.

[0028] Some seed treatments incorporate preventative treatments and enhancements, such as treatments with pesticides (fungicides and / or insecticides, etc.) in combination with one or more plant-derived agents and / or inoculants.

[0029] As disclosed in the previously cited references, a variety of different materials are used as binders in aqueous seed coating compositions.

[0030] For example, the binder materials disclosed in Patent Documents 8 to 15 generally include polyvinyl alcohol homopolymers, copolymers, and functionally modified and / or cross-linked versions thereof.

[0031] Several of the commercially available polymeric binders, including several polyvinyl alcohols, suffer from low water solubility / dipole solubility, low seed cover mobility, high levels of dusting, and / or lack of vegetative properties.

[0032] For example, seed coating additives optimized for dust reduction may result in poor seed flowability. This can be explained by the fact that ingredients added to increase the adhesion of the coating are less susceptible to dust, and adhesion that reduces dusting often creates flowability issues, thus potentially leading to unacceptable flow and flatness properties.

[0033] On the other hand, factors that increase the flowability of coated seeds can have a negative impact on dust emission characteristics. For mechanical planting of seeds, it is essential that the seeds do not aggregate. Seeds coated with insufficiently hydrophobic polymer binders tend to stick to each other when exposed to warm, humid air, such as encountered in summer in storage rooms.

[0034] There is a need to improve long term storage stability, maintain or improve seed germination and seed handling characteristics, and provide a water based, biodegradable and cost effective seed coating with low dusting characteristics.

[0035] In addition to its use as a fiber and film raw material, PVA is also widely used as a paper processing agent, a fiber processing agent, an inorganic binder, an adhesive, a stabilizer for emulsion polymerization and suspension polymerization, etc., taking advantage of its water-soluble properties. In particular, PVA is known as a dispersion stabilizer for emulsion polymerization of vinyl ester monomers represented by vinyl acetate, and vinyl ester aqueous emulsions obtained by emulsion polymerization using PVA as a dispersion stabilizer for emulsion polymerization are widely used in various adhesives, coating bases, coating agents, various adhesives for impregnated paper and non-woven products, such as adhesives, admixtures, concrete bonding materials, paper processing, fiber processing, and other fields.

[0036] For example, Patent Document 21 discloses an aqueous emulsion having high-speed coating properties and excellent initial adhesion.

[0037] Patent Document 22 discloses a woodworking adhesive having excellent water-resistant adhesiveness by using PVA containing 1 to 10 mol % of ethylene units.

[0038] PVA is usually used as a dispersant for suspension polymerization of vinyl chloride. In suspension polymerization, a vinyl compound dispersed in an aqueous medium is polymerized using an oil-soluble catalyst to obtain a granular vinyl polymer. At this time, a dispersant is added to the aqueous medium for the purpose of improving the quality of the resulting polymer. The dominant factors of the quality of the vinyl polymer obtained by suspension polymerization of the vinyl compound are: polymerization rate, ratio of water to the vinyl compound (monomer), polymerization temperature, type and amount of the oil-soluble catalyst, form of the polymerization container, stirring speed of the contents in the polymerization container, and type of dispersant, etc. Among them, the type of dispersant has a significant impact on the quality of the vinyl polymer, such as particle size distribution or plasticizer absorption. PVA is used as a dispersant alone, or, in combination with PVA or cellulose derivatives such as methylcellulose and carboxymethylcellulose, it is used as a dispersant.

[0039] For example, there is an example of using PVA as a dispersion stabilizer for suspension polymerization. In Non-Patent Document 1, as dispersants used in suspension polymerization of vinyl chloride, PVA with a degree of polymerization of 2000 and a saponification degree of 80 mol% and PVA with a degree of polymerization of 700 to 800 and a saponification degree of 70 mol% are disclosed.

[0040] In addition, Patent Document 23 discloses a dispersant containing PVA, wherein the average degree of polymerization of the PVA is greater than 500, the ratio of the weight average degree of polymerization Pw to the number average degree of polymerization Pn (Pw / Pn) is less than 3.0, and the PVA has a structure [-CO-(CH=CH)2] containing a carbonyl group and an adjacent vinylene group, the absorbance of a 0.1% aqueous solution at wavelengths of 280 nm and 320 nm is greater than 0.3 and greater than 0.15, respectively, and the ratio (b) / (a) of the absorbance (b) at a wavelength of 320 nm to the absorbance (a) at a wavelength of 280 nm is greater than 0.30.

[0041] It is conventionally known that partially saponified vinyl alcohol polymers are used as dispersants for suspension polymerization of vinyl compounds (e.g., vinyl chloride). However, when conventional partially saponified PVA is used, it is not possible to obtain the properties required of the resulting vinyl resin, specifically, (1) high plasticizer absorption even when used in small amounts, (2) absence of foreign matter such as fish eyes, (3) easy removal of residual monomer components, (4) less formation of coarse particles, etc.

[0042] In order to meet the above-mentioned required performance, there have been proposed methods such as using PVA with a low degree of polymerization, a low degree of saponification and an oxyalkylene group in the side chain as a dispersing aid for suspension polymerization of vinyl compounds (see patent documents 24 to 30); a method of using PVA with an ionic group (see patent document 31); a method of using PVA with an alkyl group at the end to prepare an aqueous solution in advance and putting it into a polymerization tank (see patent document 32), etc.

[0043] It is difficult to provide a vinyl alcohol polymer having the same or more properties than the vinyl alcohol polymer derived only from petroleum, and it is possible to save petroleum resources and suppress the emission of carbon dioxide in the manufacturing process. Therefore, in order to reduce the consumption of petroleum resources, it is also studied to change the composition of the resin combination according to the purpose, and develop a packaging bag (with reference to patent documentation 33) of a biodegradable resin composition containing a biodegradable resin other than petroleum-derived raw materials in the resin combination. However, in this case, compared with the material of petroleum-based resins, it is difficult to improve productivity due to the significantly poor processing adaptability such as tensile strength, tear strength, sealing strength, hardness, and it is also difficult to improve durability (for example, with reference to paragraph 0004 of Japanese Patent Laid-Open No. 2021-14311).

[0044] Prior art literature

[0045] Patent Literature

[0046] Patent Document 1: Japanese Patent Application Publication No. 2000-119585

[0047] Patent Document 2: International Publication No. 2019 / 031613

[0048] Patent Document 3: International Publication No. 2019 / 131939

[0049] Patent Document 4: International Publication No. 2019 / 131952

[0050] Patent Document 5: Japanese Patent Application Publication No. 2000-119585

[0051] Patent Document 6: Japanese Patent Application Publication No. 2017-43872

[0052] Patent Document 7: U.S. Patent Application Publication No. 3698133

[0053] Patent Document 8: U.S. Patent Application Publication No. 3707807

[0054] Patent Document 9: U.S. Patent Application Publication No. 3947996

[0055] Patent Document 10: U.S. Patent Application Publication No. 4249343

[0056] Patent Document 11: U.S. Patent Application Publication No. 4272417

[0057] Patent Document 12: U.S. Patent Application Publication No. 5849320

[0058] Patent Document 13: U.S. Patent Application Publication No. 5,876,739

[0059] Patent Document 14: U.S. Patent No. 90101131

[0060] Patent Document 15: International Publication No. 2017 / 187994

[0061] Patent Document 16: U.S. Patent Application Publication No. 4729190

[0062] Patent Document 17: International Publication No. 90 / 11011

[0063] Patent Document 18: International Publication No. 2005 / 062899

[0064] Patent Document 19: International Publication No. 2008 / 037489

[0065] Patent Document 20: International Publication No. 2013 / 166020

[0066] Patent Document 21: Japanese Patent No. 6647217

[0067] Patent Document 22: Japanese Patent No. 3466316

[0068] Patent Document 23: Japanese Patent Publication No. 5-88251

[0069] Patent Document 24: Japanese Patent Application Laid-Open No. 9-100301

[0070] Patent Document 25: Japanese Patent Application Laid-Open No. 10-147604

[0071] Patent Document 26: Japanese Patent Application Laid-Open No. 10-259213

[0072] Patent Document 27: Japanese Patent Application Laid-Open No. 11-217413

[0073] Patent Document 28: Japanese Patent Application Publication No. 2001-040019

[0074] Patent Document 29: Japanese Patent Application Publication No. 2002-069105

[0075] Patent Document 30: Japanese Patent Application Publication No. 2007-063369

[0076] Patent Document 31: Japanese Patent Application Laid-Open No. 10-168128

[0077] Patent Document 32: International Publication No. 2015 / 019614

[0078] Patent Document 33: Japanese Patent Application Publication No. 2009-155516

[0079] Non-patent literature

[0080] Non-patent document 1: "Polymer Publishing House", published in 1984, pp. 369-373 and 411. Summary of the invention

[0081] Problems to be solved by the invention

[0082] A vinyl alcohol polymer having properties equivalent to or better than those of vinyl alcohol polymers derived solely from petroleum, capable of saving petroleum resources and suppressing carbon dioxide emissions during the production process has not yet been obtained.

[0083] The object of the present invention is to provide a vinyl alcohol polymer having properties equal to or better than those of vinyl alcohol polymers derived solely from petroleum. In addition, the object of the present invention is to provide a vinyl alcohol polymer having properties equal to or better than those of vinyl alcohol polymers derived solely from petroleum, and to save petroleum resources and suppress carbon dioxide emissions during the manufacturing process when using a vinyl alcohol polymer (PVA).

[0084] Furthermore, another object of the present invention is to save petroleum resources and suppress carbon dioxide emissions in the manufacturing process when using a vinyl alcohol polymer (PVA) as a slurry additive, drilling mud, cement slurry, underground treatment filler, multilayer structure with excellent oxygen barrier properties, a method for producing the same and a packaging material having the same, a paper coating agent, coated paper, a seed coating composition, an aqueous emulsion, an adhesive, a dispersion stabilizer for suspension polymerization of a vinyl compound, and a dispersion stabilization aid for suspension polymerization of a vinyl compound. In addition, another object of the present invention is to provide an underground treatment filler containing a vinyl alcohol polymer (PVA) that does not have a poor appearance.

[0085] Means used to solve problems

[0086] As a result of intensive studies, the present inventors have found that the above-mentioned object can be achieved by using a plant-derived vinyl ester monomer as a part thereof and using a vinyl alcohol polymer obtained by polymerizing and saponifying the vinyl ester monomer, thereby completing the present invention.

[0087] That is, the following inventions are included.

[0088] [1] A vinyl alcohol polymer (X) obtained by polymerizing a plant-derived vinyl ester monomer (A) and a petroleum-derived vinyl ester monomer (B) and saponifying the polymer, wherein the molar ratio of (A) / (B) is 5 / 95 to 100 / 0.

[0089] [2] The vinyl alcohol polymer (X) according to [1], further comprising ethylene units, wherein the content of the ethylene units is 1 mol% or more and less than 20 mol%.

[0090] [3] A slurry additive comprising the vinyl alcohol polymer (X) according to [1] or [2].

[0091] [4] A drilling mud comprising the slurry additive described in [3].

[0092] [5] The drilling mud according to [4], further comprising water and bentonite.

[0093] [6] Cement slurry containing the slurry additive described in [3].

[0094] [7] The cement slurry according to [6], further comprising a liquid agent and a curable powder.

[0095] [8] A filler for underground treatment, comprising the vinyl alcohol polymer (X) according to [1] or [2],

[0096] The molar ratio of (A) / (B) is 5 / 95 to 90 / 10.

[0097] [9] The underground treatment filler according to [8], wherein the vinyl alcohol polymer (X) contains another unsaturated monomer (C) copolymerizable with the vinyl ester monomer.

[0098]

[10] The filler for underground treatment according to [8] or [9], further comprising a plasticizer.

[0099]

[11] A multilayer structure comprising: a layer (C) containing the vinyl alcohol polymer (X) according to [1] or [2]; and a layer (D) containing a resin,

[0100] The aforementioned resin is at least one resin selected from polyolefin resin, polyester resin, polyamide resin, polyvinyl chloride (PVC) resin, ABS resin, polylactic acid (PLA) resin, polybutylene succinate (PBS) resin, polyhydroxyalkanoate (PHA) resin, polyhydroxybutyrate / hydroxyhexanoate (PHBH) resin, starch and cellulose.

[0101]

[12] The method for producing a multilayer structure according to

[11] , comprising: preparing an aqueous solution containing the vinyl alcohol polymer (X) to obtain a coating agent; and applying the coating agent to the surface of a substrate containing a resin.

[0102] The aforementioned resin is at least one resin selected from polyolefin resin, polyester resin, polyamide resin, polyvinyl chloride (PVC) resin, ABS resin, polylactic acid (PLA) resin, polybutylene succinate (PBS) resin, polyhydroxyalkanoate (PHA) resin, polyhydroxybutyrate / hydroxyhexanoate (PHBH) resin, starch and cellulose.

[0103]

[13] A packaging material comprising the multilayer structure described in

[11] .

[0104]

[14] A paper coating agent comprising the vinyl alcohol polymer (X) according to [1] or [2].

[0105]

[15] Coated paper, which is obtained by coating the paper coating agent described in

[14] on paper.

[0106]

[16] The coated paper according to

[15] , which is a release paper base paper.

[0107]

[17] The coated paper according to

[15] , which is oil-resistant paper.

[0108]

[18] A seed coating composition comprising the vinyl alcohol polymer (X) according to [1] or [2].

[0109]

[19] The seed coating composition according to

[18] , further comprising one or more hydrophobic pesticides.

[0110]

[20] an aqueous emulsion comprising a dispersant and a dispersoid,

[0111] The aforementioned dispersoid comprises a polymer (Y1) containing ethylenically unsaturated monomer units,

[0112] The dispersant contains the vinyl alcohol polymer (X) described in [1] or [2].

[0113]

[21] An aqueous emulsion according to

[20] , wherein the polymer (Y1) containing ethylenically unsaturated monomer units is a polymer having specific units derived from at least one selected from vinyl ester monomers, (meth)acrylate monomers, styrene monomers and diene monomers, and the content of the above-mentioned units in the polymer relative to all monomer units is 70% by mass or more.

[0114]

[22] The aqueous emulsion according to

[20] or

[21] , further comprising a polyisocyanate compound.

[0115]

[23] An adhesive comprising the aqueous emulsion according to any one of

[20] to

[22] .

[0116]

[24] A dispersion stabilizer for suspension polymerization of a vinyl compound, comprising the vinyl alcohol polymer (X) described in [1] or [2].

[0117]

[25] A method for producing a vinyl resin, comprising the step of performing suspension polymerization of a vinyl compound in the presence of the dispersion stabilizer for suspension polymerization described in

[24] .

[0118]

[26] The method for producing a vinyl resin according to

[25] , comprising: a step of performing suspension polymerization of a vinyl compound in the presence of the aforementioned dispersion stabilizer for suspension polymerization and a further dispersion stabilization auxiliary agent,

[0119] The dispersion stabilization aid comprises a vinyl alcohol polymer (Y2) having a saponification degree of less than 65 mol %.

[0120]

[27] A dispersion stabilization aid for suspension polymerization of a vinyl compound, comprising the vinyl alcohol polymer (X) described in [1] or [2],

[0121] The degree of saponification of the vinyl alcohol polymer (X) is 20 mol% or more and less than 60 mol%.

[0122]

[28] A method for producing a vinyl resin, comprising: carrying out a suspension polymerization of a vinyl compound in the presence of the dispersion stabilization auxiliary agent for suspension polymerization and a dispersion stabilizer for suspension polymerization as described in

[27] ,

[0123] The dispersion stabilizer for suspension polymerization contains a vinyl alcohol polymer (Y3) having a saponification degree of 65 mol % or more and a viscosity average polymerization degree of 600 or more.

[0124]

[29] The method for producing a vinyl resin according to

[28] , wherein the mass ratio of the dispersion stabilizer to the dispersion stabilization aid (dispersion stabilizer / dispersion stabilization aid) is 95 / 5 to 20 / 80.

[0125] Effects of the Invention

[0126] According to the present invention, by making a part of PVA a plant-derived substance, a vinyl alcohol polymer having properties equal to or better than those of vinyl alcohol polymers derived only from petroleum can be provided. Therefore, according to the present invention, petroleum resources can be saved, and the emission of carbon dioxide in the manufacturing process can be reduced to suppress global warming.

[0127] In addition, according to the present invention, by making a part of PVA used for various purposes such as slurry additives, drilling mud, cement slurry, underground treatment fillers, multilayer structures with excellent oxygen barrier properties, their production methods and packaging materials equipped with them, paper coating agents, aqueous emulsions, adhesives, seed coating compositions, dispersion stabilizers for suspension polymerization of vinyl compounds, and dispersion stabilization aids for suspension polymerization of vinyl compounds into substances derived from plants, it is possible to save petroleum resources, reduce carbon dioxide emissions in the production process, and inhibit global warming.

[0128] According to the present invention, a filler for underground treatment containing a vinyl alcohol polymer (PVA) having no appearance defects can be provided. According to the present invention, a multilayer structure having excellent gas barrier properties under high humidity and a packaging material having the same can be provided. DETAILED DESCRIPTION

[0129] Hereinafter, embodiments for carrying out the present invention will be described.

[0130] [Vinyl alcohol polymer (X)]

[0131] The vinyl alcohol polymer (X) of the present invention is a vinyl alcohol polymer (X) (hereinafter sometimes abbreviated as PVA (X)) obtained by polymerizing and saponifying a plant-derived vinyl ester monomer (A) and a petroleum-derived vinyl ester monomer (B), wherein the molar ratio of (A) / (B) is 5 / 95 to 100 / 0.

[0132] The plant-derived vinyl ester monomer (A) (hereinafter also referred to as "vinyl ester monomer (A)") refers to a vinyl ester monomer (preferably vinyl acetate) obtained by reacting ethylene (hereinafter also referred to as bioethylene) obtained from plant raw materials such as sugar cane and corn with a lower carboxylic acid such as acetic acid. The biomass may be a single non-fossil raw material or a mixture of non-fossil raw materials, and examples thereof include cellulose crops (pulp, kenaf, wheat straw, rice straw, waste paper, papermaking residue, etc.), wood, charcoal, compost, natural rubber, cotton, sugar cane, bean curd residue, oils and fats (rapeseed oil, cottonseed oil, soybean oil, coconut oil, castor oil, etc.), carbohydrate crops (corn, potatoes, wheat, rice, rice husk, rice bran, old rice, cassava, sago palm, etc.), bagasse, buckwheat, soybean, essential oils (pine oil, orange oil, eucalyptus oil, etc.), pulp black liquor, and vegetable oil residue. In addition, biomass is not limited to biofuel harvests, and agricultural residues, urban waste, industrial waste, sediments from the paper industry, waste from pastures, wood, forest waste, etc. can also be listed. More specifically, as an example, the sugar solution taken out from sugar cane or corn is heated, concentrated and crystallized, and the raw sugar and waste syrup obtained thereby are separated by a centrifuge, and the waste syrup is diluted with water to an appropriate concentration, and fermented by yeast to produce ethanol (bioethanol), and the bioethanol is heated and obtained by intramolecular dehydration reaction in the presence of a catalyst. In other examples, pulp black liquor is treated with an acid or an enzyme to produce ethanol (bioethanol), and ethylene is obtained in the same manner. On the other hand, the petroleum-derived vinyl ester monomer (B) (hereinafter also referred to as "vinyl ester monomer (B)") refers to a vinyl ester monomer obtained using ethylene derived from naphtha that is commonly obtained as a raw material.

[0133] PVA (X) is synthesized by saponifying a vinyl ester polymer obtained by polymerizing a plant-derived vinyl ester monomer (A) and a petroleum-derived vinyl ester monomer (B).

[0134] As the polymerization method of the vinyl ester monomer, for example, bulk polymerization, solution polymerization, suspension polymerization, emulsion polymerization, dispersion polymerization, etc. can be listed. From the industrial point of view, solution polymerization, emulsion polymerization or dispersion polymerization is preferred. The polymerization of the vinyl ester monomer can be any polymerization method of a batch method, a semi-batch method and a continuous method.

[0135] Examples of the vinyl ester monomers (vinyl ester monomers (A) and vinyl ester monomers (B)) include vinyl acetate, vinyl formate, vinyl propionate, vinyl octanoate, and vinyl tertiary carboxylic acid esters. Among these, vinyl acetate is preferred from an industrial point of view. The vinyl ester monomers (A) and (B) may be the same compound (e.g., vinyl acetate) or different compounds. That is, PVA (X) may be a homopolymer of one vinyl ester monomer or a copolymer of different vinyl ester monomers.

[0136] The polymerization initiator used in the polymerization is selected from known polymerization initiators, such as azo initiators, peroxide initiators, and redox initiators, depending on the polymerization method. Examples of azo initiators include 2,2'-azobisisobutyronitrile, 2,2'-azobis(2,4-dimethylvaleronitrile), and 2,2'-azobis(4-methoxy-2,4-dimethylvaleronitrile). Examples of peroxide initiators include peroxydicarbonate compounds such as diisopropyl peroxydicarbonate, di(2-ethylhexyl) peroxydicarbonate, and diethoxyethyl peroxydicarbonate; perester compounds such as tert-butyl peroxyneodecanoate and α-cumyl peroxyneodecanoate; acetylcyclohexylsulfonyl peroxide; and 2,4,4-trimethylpentyl 2-peroxyphenoxyacetate. Potassium persulfate, ammonium persulfate, hydrogen peroxide, and the like can be combined with the above-mentioned initiators to prepare a polymerization initiator. The redox initiator is a polymerization initiator obtained by combining the above-mentioned peroxide initiator or oxidant (potassium persulfate, ammonium persulfate, hydrogen peroxide, etc.) with a reducing agent such as sodium bisulfite, sodium bicarbonate, tartaric acid, L-ascorbic acid, Rongalite, etc. The amount of the polymerization initiator used varies depending on the polymerization catalyst, so it cannot be generalized and is selected according to the polymerization rate.

[0137] Furthermore, PVA (X) may be obtained by saponifying a vinyl ester copolymer obtained by copolymerizing a vinyl ester monomer (vinyl ester monomer (A) and vinyl ester monomer (B)) and another copolymerizable unsaturated monomer within a range not impairing the gist of the present invention. Examples of the other unsaturated monomers include α-olefins such as ethylene, propylene, n-butene, and isobutylene; acrylic acid and its salts; acrylic acid esters such as methyl acrylate, ethyl acrylate, n-propyl acrylate, isopropyl acrylate, n-butyl acrylate, isobutyl acrylate, tert-butyl acrylate, 2-ethylhexyl acrylate, dodecyl acrylate, and octadecyl acrylate; methacrylic acid and its salts; methacrylic acid esters such as methyl methacrylate, ethyl methacrylate, n-propyl methacrylate, isopropyl methacrylate, n-butyl methacrylate, isobutyl methacrylate, tert-butyl methacrylate, 2-ethylhexyl methacrylate, dodecyl methacrylate, and octadecyl methacrylate; acrylamide; N-methylacrylamide, N-ethylacrylamide, N,N-dimethylacrylamide, diacetoneacrylamide, acrylamidopropanesulfonic acid and its salts, acrylamidopropyldimethylamine and its salts or quaternary salts thereof, N-hydroxypropyldimethylamine, Acrylamide derivatives such as methacrylamide and its derivatives; methacrylamide; methacrylamide derivatives such as N-methyl methacrylamide, N-ethyl methacrylamide, methacrylamide propanesulfonic acid and its salts, methacrylamide propyl dimethylamine and its salts or quaternary salts, N-hydroxymethyl methacrylamide and its derivatives; vinyl ethers such as methyl vinyl ether, ethyl vinyl ether, n-propyl vinyl ether, isopropyl vinyl ether, n-butyl vinyl ether, isobutyl vinyl ether, tert-butyl vinyl ether, dodecyl vinyl ether, stearyl vinyl ether; nitriles such as acrylonitrile and methacrylonitrile; vinyl halides such as vinyl chloride and vinyl fluoride; vinylidene halides such as vinylidene chloride and vinylidene fluoride; allyl compounds such as allyl acetate and allyl chloride; unsaturated dicarboxylic acids such as maleic acid, itaconic acid, and fumaric acid and their salts or monoalkyl esters or dialkyl esters; vinyl silyl compounds such as vinyltrimethoxysilane; isopropenyl acetate, etc. Among them, one or more kinds may be copolymerized. PVA having such a copolymer component is sometimes referred to as "modified PVA".

[0138] As a component copolymerized with a vinyl ester monomer, i.e., other unsaturated monomers, ethylene is sometimes particularly preferred. That is, PVA (X) sometimes preferably further comprises ethylene units. When PVA (X) also comprises ethylene units, the lower limit of the content of ethylene units can be more than 0 mol%, and can be more than 0.1 mol%. The content of the content of ethylene units is preferably more than 1 mol% and less than 20 mol%. The content of ethylene units is more preferably more than 1.5 mol%, and further more preferably more than 2 mol%. On the other hand, the content of ethylene units is suitable for less than 15 mol%, more preferably less than 10 mol%, and further more preferably less than 8.5 mol%. When ethylene is used as a copolymerization component, the ethylene can be a conventional substance manufactured from a raw material derived from petroleum, can also be made of the above-mentioned bioethanol as a raw material, or can also be a mixture of the two.

[0139] In the use of slurry additives, drilling mud and cement slurry, it is particularly preferred that PVA (X) is obtained by copolymerizing ethylene with a vinyl ester monomer (A) and a vinyl ester monomer (B). By copolymerizing ethylene with a vinyl ester, the solubility of the saponified PVA (X) can be reduced. Thus, dehydration from the slurry at high temperature and an increase in the viscosity of the slurry can be further suppressed.

[0140] The content of ethylene units in PVA (X) is preferably less than 10 mol% of all structural units of PVA (X), more preferably less than 9 mol%, and further preferably less than 8 mol%, from the viewpoint of having properties equivalent to or better than those of vinyl alcohol polymers derived solely from petroleum in the use of slurry additives, drilling muds, and cement slurries. In the case where PVA (X) is a copolymer containing ethylene units in its structural units, the lower limit of the content of ethylene units may be greater than 0 mol%, and may be greater than 0.1 mol%, or may be greater than 1 mol%.

[0141] The content of ethylene units in PVA (X) is determined by the content of vinyl ester polymer, which is the precursor of PVA (X). 1 That is, the vinyl ester polymer as a precursor was fully reprecipitated and purified three or more times using a mixed solution of n-hexane and acetone, and then dried under reduced pressure at 80°C for three days to prepare a vinyl ester polymer for analysis. The vinyl ester polymer was dissolved in DMSO-d6 and 500 MHz 1 H-NMR (JEOL GX-500) was measured at 80° C. The content of ethylene units was calculated using the peak of the main chain methine group derived from vinyl ester (integrated value P: 4.7 ppm to 5.2 ppm) and the peak of the main chain methylene group derived from ethylene, vinyl ester and the third component (integrated value Q: 0.8 ppm to 1.6 ppm).

[0142] Ethylene unit content (mol%) = 100 × ((Q-2P) / 4) / P

[0143] As described above, other unsaturated monomers copolymerizable with vinyl ester monomers may be copolymerized in PVA(X). PVA(X) obtained by copolymerization with unsaturated monomers such as unsaturated monocarboxylic acids, unsaturated dicarboxylic acids or their salts, their monoalkyl esters or dialkyl esters has a structural unit containing carboxylic acid, and therefore has better water solubility. When used as a filler for underground treatment, a paper coating agent, a seed coating composition, or a dispersion stabilizer for suspension polymerization of vinyl compounds, it is preferred from the viewpoint of more moderate dissolution and less environmental burden.

[0144] In the use of fillers for underground treatment, paper coating agents, seed coating compositions, and dispersion stabilizers for suspension polymerization of vinyl compounds, when PVA (X) is a modified PVA, the modification rate of the modified PVA, that is, the content of structural units derived from "other unsaturated monomers capable of copolymerizing with vinyl ester monomers" relative to all structural units constituting the modified PVA is preferably from 0.5 mol% to 10 mol%, more preferably from 0.7 mol% to 8 mol%, and further preferably from 1.0 mol% to 5 mol%.

[0145] It should be noted that the modification rate in the modified PVA can be calculated based on the saponification degree of the PVA resin of 100 mol %. 1 The modification rate can be determined by H-NMR spectrum (solvent: DMSO-d6, internal standard: tetramethylsilane). Specifically, the modification rate can be calculated based on the peak areas of protons derived from hydroxyl groups in the modified group, methine protons and methylene protons, methylene protons in the main chain, and protons of hydroxyl groups linked to the main chain.

[0146] As a component copolymerized with a vinyl ester monomer in the use of a paper coating agent, a multilayer structure and a packaging material using it, an aqueous emulsion and an adhesive using it, i.e., other unsaturated monomers, ethylene is particularly preferred. The content of ethylene units in the PVA (X) containing ethylene units is preferably 1 mol% or more and less than 20 mol%. When the content of ethylene units is 1 mol% or more, the gas barrier properties of the obtained PVA (X) are more excellent. The content of ethylene units is more preferably 1.5 mol% or more, and further preferably 2 mol% or more. On the other hand, when the content of ethylene units is less than 20 mol%, PVA (X) has appropriate water solubility and is easily prepared in the form of an aqueous solution. The content of ethylene units is suitable for less than 15 mol%, more preferably less than 10 mol%, and further preferably less than 8.5 mol%. When ethylene is used as a copolymerization component, the ethylene can be a conventional substance manufactured from a raw material derived from petroleum, or it can be made from the above-mentioned bioethanol, or it can be a mixture of the two. When PVA (X) is a copolymer containing ethylene units in the structural units, the lower limit of the content of the ethylene units may be more than 0 mol %, and may be 0.1 mol % or more, or 1 mol % or more.

[0147] During the polymerization of vinyl ester monomer (A) and vinyl ester monomer (B), a chain transfer agent may also coexist for the purpose of adjusting the degree of polymerization of PVA (X). Examples of chain transfer agents include aldehydes such as acetaldehyde, propionaldehyde, butyraldehyde, and benzaldehyde; ketones such as acetone, methyl ethyl ketone, hexanone, and cyclohexanone; thiols such as 2-hydroxyethanethiol; thiocarboxylic acids such as 3-mercaptopropionic acid and thioacetic acid; halogenated hydrocarbons such as trichloroethylene and perchloroethylene, among which aldehydes or ketones are preferred. The amount of chain transfer agent added can be determined based on the chain transfer constant of the chain transfer agent, the degree of polymerization of PVA to be achieved, and the like.

[0148] As the saponification reaction of the vinyl ester polymer, a known alcoholysis and / or hydrolysis reaction using a basic catalyst such as sodium hydroxide, potassium hydroxide, sodium methoxide, or an acidic catalyst such as p-toluenesulfonic acid can be applied.

[0149] As the solvent used in the saponification reaction, alcohols such as methanol and ethanol; esters such as methyl acetate and ethyl acetate; ketones such as acetone and methyl ethyl ketone; aromatic hydrocarbons such as benzene and toluene, etc. can be listed, and they can be used alone or in combination of two or more. Among them, it is convenient to use methanol or a mixed solution of methanol and methyl acetate as a solvent and perform the saponification reaction in the presence of sodium hydroxide as an alkaline catalyst, so it is preferred.

[0150] (Saponification degree)

[0151] In the use of slurry additives, drilling mud and cement slurry, the saponification degree of PVA (X) is preferably 99 mol% or more, more preferably 99.5 mol% or more. PVA is a crystalline polymer having a crystalline part caused by hydrogen bonds of hydroxyl groups contained. The crystallinity of PVA (X) increases with the increase of the saponification degree, and the increase of the crystallinity reduces the water solubility of PVA (X). In particular, the solubility of PVA (X) in high temperature water changes significantly with a saponification degree of 99.5 mol% as the limit. Therefore, PVA (X) with a saponification degree of 99.5 mol% or more sometimes has high water resistance (low solubility) due to the strength of its hydrogen bonds, and has water resistance comparable to that of PVA (X) with chemical crosslinking. Therefore, by making the saponification degree of PVA (X) above 99.5 mol%, even if PVA (X) is not chemically crosslinked, it is possible to suppress the dehydration and high viscosity of the slurry, and as a result, it is advantageous in terms of cost corresponding to the process of chemical crosslinking that can be omitted. In particular, when used as an additive for cement slurry, if the saponification degree is low, dehydration at high temperature may not be sufficiently suppressed.

[0152] In addition, the saponification degree of PVA(X) is a value measured according to JIS K6726:1994.

[0153] In the use of underground treatment fillers and paper coating agents, the saponification degree of PVA (X) is preferably 90 mol% or more, more preferably 98 mol% or more, further preferably 99 mol% or more, and particularly preferably 99.5 mol% or more. PVA is a crystalline polymer having a crystalline part caused by hydrogen bonds of the hydroxyl groups contained. The crystallinity of PVA (X) increases with the increase of the saponification degree, and the increase of the crystallinity reduces the water solubility of PVA (X).

[0154] In the use of the multilayer structure and the packaging material using the same, the saponification degree of PVA (X) is not particularly limited, and is preferably 80 to 99.99 mol%. When the saponification degree is 80 mol% or more, the oxygen barrier property of the obtained multilayer structure is more excellent. The saponification degree is more preferably 85 mol% or more, and further preferably 90 mol% or more. On the other hand, when the saponification degree is 99.99 mol% or less, PVA (X) can be stably manufactured. The saponification degree is more preferably 99.5 mol% or less, further preferably 99 mol% or less, and particularly preferably 98.5 mol% or less.

[0155] In the use of the seed coating composition, the saponification degree of PVA (X) is preferably 65 mol% or more, more preferably 67 mol% or more, further preferably 69 mol% or more, and particularly preferably 70 mol% or more. If the saponification degree of PVA (X) is 60 mol% or more, the water solubility of PVA (X) is better, which is more advantageous in the production of the seed coating composition.

[0156] In the use of aqueous emulsions and adhesives using the same, the saponification degree of PVA (X) is not particularly limited, and is preferably 80 to 99.99 mol%. By making the saponification degree 80 mol% or more, it is sometimes possible to further suppress the aggregation of particles of the aqueous emulsion during storage, and the stability can be made better. The saponification degree is more preferably 82 mol% or more, and further preferably 85 mol% or more. On the other hand, by making the saponification degree 99.99 mol% or less, there is a tendency to make the particles of the aqueous emulsion more stable and easier to manufacture. The saponification degree is more preferably 99.5 mol% or less, further preferably 99 mol% or less, and particularly preferably 98.5 mol% or less.

[0157] In the purpose of suspension polymerization dispersion stabilizer of vinyl compounds, the saponification degree of PVA (X) is preferably 60 mol% or more and 99.5 mol% or less, more preferably 65 mol% or more and 99.2 mol% or less, and further preferably 68 mol% or more and 99.0 mol% or less. When the saponification degree is 60 mol% or more, the water solubility of PVA (X) is excellent, and it is easy to prepare dispersion stabilizer aqueous solution. On the other hand, if the saponification degree is 99.5 mol% or less, then when using the obtained dispersant for suspension polymerization, the formation of a large amount of coarse particles can be further suppressed. In addition, sometimes the obtained vinyl polymer particles have high porosity and excellent plasticizer absorption.

[0158] In the purposes of the suspension polymerization of vinyl compounds with dispersion stabilization auxiliary agent, the saponification degree of PVA (X) is more than 20 mol % and less than 60 mol %, preferably more than 25 mol % and below 58 mol %, more preferably more than 30 mol % and below 56 mol %. When the saponification degree is below 20 mol %, it is difficult to manufacture PVA (X). On the other hand, if the saponification degree is more than 60 mol %, it is sometimes difficult to remove the monomer component from the vinyl polymer particles obtained by the suspension polymerization of vinyl compounds, or the plasticizer absorbency of the obtained vinyl polymer particles is reduced.

[0159] (Degree of Polymerization)

[0160] In the use of slurry additives, drilling mud and cement slurry, the degree of polymerization of PVA (X) is preferably 1,500 or more and 4,500 or less, and more preferably 2,000 or more and 3,800 or less. When the degree of polymerization of PVA (X) is 4,500 or less, when PVA (X) is used as the cement slurry additive, a suitable viscosity can be obtained even at high temperatures. On the other hand, when the degree of polymerization of PVA (X) is 1,500 or more, dehydration can be sufficiently suppressed even at high temperatures.

[0161] In the use of fillers for underground treatment, paper coating agents, seed coating compositions, and dispersion stabilizers for suspension polymerization of vinyl compounds, the degree of polymerization of PVA (X) is preferably 150 or more and 5,000 or less, more preferably 300 or more and 4,000 or less, and further preferably 500 or more and 3,500 or less. When the degree of polymerization of PVA (X) is 5,000 or less, it is industrially advantageous from the perspective of the manufacturability of PVA (X). On the other hand, in the use of fillers for underground treatment, if the degree of polymerization of PVA (X) is 150 or more, a more appropriate filling effect can be obtained. In addition, in the use of paper coating agents, if the degree of polymerization of PVA (X) is 150 or more, a more appropriate water resistance can be imparted to the coated paper. In the use of seed coating compositions, if the degree of polymerization of PVA (X) is 150 or more, the effect based on coating is more excellent. When the degree of polymerization of PVA(X) is 150 or more, it is more advantageous in the production of PVA(X) and has better performance as a dispersion stabilizer for suspension polymerization.

[0162] In the use of multilayer structures and packaging materials using the same, the degree of polymerization of PVA (X) is preferably 150 or more and 5,000 or less, and more preferably 200 or more and 5,000 or less. When the degree of polymerization of PVA (X) is 150 or more, it is more advantageous in the manufacture of the multilayer structure. The degree of polymerization is further preferably 250 or more, further preferably 300 or more, and particularly preferably 400 or more. On the other hand, when the degree of polymerization of PVA (X) is 5,000 or less, the viscosity of the aqueous solution will not be too high, and the handling properties can be made better. The degree of polymerization of PVA (X) is further preferably 4500 or less, further preferably 4000 or less, and particularly preferably 3500 or less.

[0163] In the use of paper coating agents, the degree of polymerization of PVA (X) is preferably 150 or more and 5,000 or less, and more preferably 300 or more and 4,000 or less. When the degree of polymerization of PVA (X) is 5,000 or less, it is more advantageous in the production of PVA (X). On the other hand, when the degree of polymerization of PVA (X) is 150 or more, it is possible to impart more appropriate water resistance to coated paper.

[0164] In the use of aqueous emulsions and adhesives using the same, the degree of polymerization of PVA (X) is preferably 150 or more and 5,000 or less, and more preferably 200 or more and 5,000 or less. When the degree of polymerization of PVA (X) is 150 or more, the storage stability of the resulting aqueous emulsion can be improved. The degree of polymerization is further preferably 250 or more, further preferably 300 or more, and particularly preferably 400 or more. On the other hand, when the degree of polymerization of PVA (X) is 5,000 or less, the viscosity of the aqueous solution will not be too high, and the handling properties can be improved. The degree of polymerization of PVA (X) is further preferably 4500 or less, further preferably 4000 or less, and particularly preferably 3500 or less.

[0165] In the use of dispersion stabilization aids for suspension polymerization of vinyl compounds, the degree of polymerization of PVA (X) is preferably 100 or more and 700 or less, more preferably 120 or more and 650 or less, and further preferably 150 or more and 600 or less. If the degree of polymerization of PVA (X) is 700 or less, it is easier to remove monomer components from the vinyl polymer particles obtained by suspension polymerization of vinyl compounds, or the plasticizer absorbency of the obtained vinyl polymer particles is improved, or when provided in the form of a high-concentration dispersion stabilization aid aqueous solution, the viscosity can be suppressed from becoming very high, and the operability is excellent. On the other hand, if the degree of polymerization of PVA (X) is 100 or more, it is more advantageous in the manufacture of PVA (X).

[0166] The degree of polymerization (viscosity average degree of polymerization) of PVA (X) is a value measured in accordance with JIS K 6726: 1994. That is, the degree of polymerization of PVA can be determined from the intrinsic viscosity [η] (dL / g) measured in water at 30°C using the following formula.

[0167] Degree of polymerization = ([η] × 1000 / 8.29) (1 / 0.62)

[0168] In the present invention, from the viewpoint of obtaining the desired effect and being industrially advantageous, the molar ratio (A) / (B) of the plant-derived vinyl ester monomer (A) to the petroleum-derived vinyl ester monomer (B) in the vinyl alcohol polymer (X) is 5 / 95 to 100 / 0. The molar ratio (A) / (B) can be set arbitrarily. By making the ratio of (A) 5 / 95 or more in terms of (A) / (B), the vinyl alcohol polymer has the same or better properties than the vinyl alcohol polymer derived only from petroleum, and the raw materials derived from plants can be fully utilized, and the effect of suppressing the environmental burden becomes greater. From the above viewpoints, the lower limit of the ratio of the plant-derived vinyl ester monomer (A) is more preferably 10 / 90, further preferably 20 / 80, and further more preferably 25 / 75 in terms of the molar ratio (A) / (B). In addition, the upper limit of the ratio of the plant-derived vinyl ester monomer (A) is preferably 90 / 10, more preferably 80 / 20, further preferably 70 / 30, particularly preferably 60 / 40, and most preferably 50 / 50 in terms of the molar ratio (A) / (B) from the perspective of the balance between environmental burden and raw material cost. If the upper limit of the ratio of the plant-derived vinyl ester monomer (A) is the above value, problems such as appearance defects such as cracks in the obtained PVA (X) are less likely to occur, which is advantageous in terms of production.

[0169] (Degree ofBiomass)

[0170] The carbon derived from biomass in the present invention means that carbon existing in the form of carbon dioxide in the atmosphere is absorbed into plants, and the carbon present in organic matter synthesized with this as a raw material can be identified by measuring radioactive carbon (i.e., carbon 14). In addition, the content ratio of components derived from biomass can be determined by measuring radioactive carbon (carbon 14). That is, since there are almost no carbon 14 atoms remaining in fossil raw materials such as petroleum, the concentration of carbon 14 in the sample to be tested is measured, and the content ratio of carbon 14 in the atmosphere (107pMC (percent Modern Carbon)) is used as an indicator and reversed, thereby being able to find the proportion of carbon in the form of biomass in the carbon contained in the sample.

[0171] The proportion of carbon derived from biomass obtained by such radiocarbon determination can be obtained as follows: for example, after the sample (vinyl ester) is converted into carbon dioxide or graphite as required, the content of carbon 14 is measured by accelerator mass spectrometry (AMS method; Accelerator Mass Spectrometry) relative to a standard substance (e.g., U.S. NIST oxalic acid) to obtain the carbon content. The proportion of carbon derived from biomass (%) can be calculated by [(amount of carbon derived from biomass in the sample) / (total carbon in the sample)×100].

[0172] The ratio of non-fossil raw materials to fossil raw materials for vinyl ester monomers can be determined by measuring the above 14 Judging by the C / C ratio, it can be distinguished from vinyl ester monomers obtained from ethylene derived from petroleum.

[0173] When ethylene derived from biomass (non-fossil raw material) is used as a part of the raw material of the vinyl ester monomer, the ratio of the non-fossil raw material of the vinyl ester monomer can be adjusted according to the amount of the obtained vinyl ester monomer. 14 C (radiocarbon) / C (carbon). In vinyl ester monomers obtained from fossil raw materials, 14 C / C is less than 1.0×10 -14 In contrast, the vinyl ester monomer (A) used in the present invention has 14 The C / C ratio is preferably 1.0×10 -14 More preferably, 1.0×10 -13 More preferably, 1.0×10 -12 For example, the carbon 14 in oxalic acid ( 14 C) content. 14 The non-fossil raw material ratio in the vinyl ester monomer can be determined by analyzing the C / C ratio.

[0174] Naturally occurring Artificially occurring due to nuclear testing in the atmosphere 14 C, therefore, sometimes 14 The C concentration is slightly higher than the standard level, and pMC may be as high as 100%, but this can be done by properly correcting the ratio of non-fossil raw materials to fossil raw materials. 14 The half-life of C is 5,730 years, which can be ignored considering the period from the manufacture to the market entry of general chemical products, especially vinyl acetate and its polymerized vinyl acetate resins and saponified products. 14 It should be noted that in the present invention, 14 C / C is 1.0×10 -14 In some cases, it can be appropriately replaced by pMC (modern carbon percentage) to express it.

[0175] The biomass content of the PVA (X) of the present invention is 5 to 90%. The measurement of the biomass content also contributes to the traceability of the carbon raw materials in the product.

[0176] It should be noted that when PVA (X) contains copolymer components such as ethylene, it is expressed in the form of biomass including the copolymer components, and the non-fossil raw material rate as the vinyl ester monomer can be calculated by calculating based on the raw material properties of the copolymer components and their modification rate.

[0177] [Additives for slurry]

[0178] The slurry additive of the present invention comprises a vinyl alcohol polymer (X) obtained by polymerizing and saponifying a vinyl ester monomer (A) derived from a plant and a vinyl ester monomer (B) derived from petroleum, wherein the molar ratio of (A) / (B) is 5 / 95 to 100 / 0. In addition, the drilling mud of the present invention comprises a vinyl alcohol polymer (X) obtained by polymerizing and saponifying a vinyl ester monomer (A) derived from a plant and a vinyl ester monomer (B) derived from petroleum, wherein the molar ratio of (A) / (B) is 5 / 95 to 100 / 0. Furthermore, the cement slurry of the present invention contains the aforementioned slurry additive.

[0179] The slurry additive of the present invention can be used as a drilling mud slurry additive and a cement slurry additive. The slurry additive contains the above-mentioned PVA (X). The PVA (X) is contained in the slurry additive in a powdered form (hereinafter, this powdered PVA (X) is also referred to as "PVA powder"). The slurry additive may contain only PVA powder, or may contain optional components on the basis of containing PVA powder. The content of PVA powder in the slurry additive is, for example, 50% by mass or more and 100% by mass or less, preferably 80% by mass or more and 100% by mass or less.

[0180] The particle size of the PVA powder is preferably a size that passes through a sieve with a nominal mesh size of 1.00 mm (16 mesh). When such PVA powder is contained in a slurry such as drilling mud or cement slurry as an additive, it is easy to suppress dehydration of the slurry at high temperature. On the other hand, the lower limit of the particle size of the PVA powder is a range in which the solubility does not become extremely large, preferably a size that does not pass through a nominal mesh size of 45 μm (325 mesh), and more preferably a size that does not pass through a nominal mesh size of 53 μm (280 mesh).

[0181] [Drilling Mud]

[0182] The drilling mud of the present invention plays the role of, for example, transporting drilled rock pieces, drilling debris, etc., improving the lubricity of drill bits and drill pipes, burying holes in porous foundations, and offsetting the reservoir pressure (pressure from magmatic rocks) generated by hydrostatic pressure. The drilling mud contains the slurry additive and has water and mud as main components. The drilling mud may contain optional components within a range that does not impair the effects of the present invention.

[0183] The drilling mud of the present invention contains PVA (X). As a suitable embodiment, a drilling mud containing PVA (X), water and mud can be cited. This drilling mud is produced by mixing mud, water, and the aforementioned slurry additive. Specifically, the drilling mud can be produced by using a water-clay suspension in which mud is dispersed and suspended in water as a base, and adding the slurry additive and optional components as needed.

[0184] <Additives for drilling mud slurry>

[0185] As a suitable embodiment, a drilling mud containing a drilling mud slurry additive can be listed. The drilling mud slurry additive contains the above-mentioned PVA powder. In addition, the drilling mud slurry additive may contain only PVA powder. In a suitable embodiment, a drilling mud containing PVA (X), water and bentonite can be listed. PVA (X) and PVA powder are as described above, so repeated description is omitted here.

[0186] Among them, in the drilling mud, as the particle size of the PVA powder, it is preferably the size that passes through a sieve with a nominal mesh size (JIS Z8801-1:2019) of 1.00 mm (16 mesh), and more preferably the size that passes through a sieve with a nominal mesh size of 500 μm (32 mesh). If the particle size of the PVA powder is the size that passes through a sieve with a nominal mesh size of 500 μm (32 mesh), the drilling mud containing the PVA powder of such a particle size can further suppress the dehydration of the drilling mud at high temperature. It should be noted that the lower limit of the particle size of the PVA powder is not particularly limited as long as it is a range in which the solubility does not become extremely large. It is preferably a size that does not pass through a nominal mesh size of 45 μm (325 mesh), and more preferably a size that does not pass through a nominal mesh size of 53 μm (280 mesh).

[0187] The content of PVA powder in the drilling mud is preferably 0.5 kg / m 3 Above and 40kg / m 3 Below, more preferably 3kg / m 3 Above and 30kg / m 3 the following.

[0188] <Mud>

[0189] Examples of the clay include bentonite, attapulgite, selenite, and hydrous magnesium silicate. Among them, bentonite is preferred.

[0190] The mixing ratio of the mud in the drilling mud is preferably 5 g to 300 g, more preferably 10 g to 200 g, per 1 kg of water used in the drilling mud.

[0191] <Optional Ingredients>

[0192] As optional components, known additives can be used, for example, copolymers of α-olefins having 2 to 12 carbon atoms and maleic anhydride or their derivatives (e.g., maleamide, maleimide) or aqueous solutions of alkali-neutralized products; dispersants, pH adjusters, defoamers, thickeners, etc. As copolymers of α-olefins having 2 to 12 carbon atoms and maleic anhydride or their derivatives, for example, copolymers of α-olefins such as ethylene, propylene, butene-1, isobutylene, diisobutylene and maleic anhydride or their derivatives (e.g., "Isobam" produced by Kuraray Co., Ltd.) can be listed, and as dispersants, for example, humic acid-based dispersants and lignin-based dispersants can be listed, among which lignin-based dispersants containing sulfonates are preferred.

[0193] [Cement slurry]

[0194] The cement slurry of the present invention is used to fix the casing in the mine and protect the inner wall of the mine by, for example, injecting it into the tubular gap between the stratum and the casing installed in the mine and solidifying it. The cement slurry contains a slurry additive, a curing powder and a liquid agent. The cement slurry may contain optional components within the range that does not impair the effect of the present invention.

[0195] Such cement slurry is produced by adding the slurry additive, the liquid agent, the curable powder, and optional components as required, and mixing them using a stirrer or the like.

[0196] <Additives for cement slurry>

[0197] As a suitable embodiment, a cement slurry containing a cement slurry additive can be listed. The cement slurry additive contains the above-mentioned PVA powder. The cement slurry additive may contain only PVA powder. In a suitable embodiment, a drilling mud containing PVA (X), a liquid agent and a curable powder can be listed. PVA and PVA powder are as described above, so repeated description is omitted here.

[0198] Among them, in the cement slurry, the particle size of the PVA powder is preferably the size that passes through a sieve with a nominal mesh of 1.00 mm (16 mesh), and more preferably the size that passes through a sieve with a nominal mesh of 250 μm (60 mesh). If the particle size of the PVA powder is the size that passes through a sieve with a nominal mesh of 250 μm (60 mesh), the cement slurry containing the PVA powder of such a particle size can further suppress the dehydration of the cement slurry at high temperature. It should be noted that as the lower limit of the particle size of the PVA powder, there is no particular limitation as long as it is a range in which the solubility does not become extremely large. It is preferably a size that does not pass through a nominal mesh of 45 μm (325 mesh), and more preferably a size that does not pass through a nominal mesh of 53 μm (280 mesh).

[0199] The content of the PVA powder in the cement paste is preferably 0.1% (BWOC) or more and 2.0% (BWOC) or less, and more preferably 0.2% (BWOC) or more and 1.0% (BWOC) or less. It should be noted that BWOC (By Weight Of Cement) refers to cement mass standard.

[0200] <Curing Powder>

[0201] Examples of curable powders include silicate cement, mixed cement, environmentally friendly cement, special cement, etc., preferably hydraulic cement that solidifies by reacting with water, and preferably geothermal well cement or oil well cement when the cement slurry is used for drilling. One type of curable powder may be used alone, or two or more types may be used in combination.

[0202] Examples of silicate cement include cement specified in JIS R5210: 2019. Specifically, examples of silicate cement include ordinary silicate cement, early strength silicate cement, super early strength silicate cement, medium heat silicate cement, low heat silicate cement, sulfate-resistant silicate cement, and low alkali silicate cement.

[0203] Examples of the mixed cement include cements specified in JIS R5211: 2019, JIS R5212: 2019, and JIS R5213: 2019, specifically, blast furnace cement, silica cement, and fly ash cement.

[0204] Special cement includes cement using silicate cement as a base, cement obtained by changing the composition or particle size structure of silicate cement, and cement having a composition different from that of silicate cement.

[0205] Examples of special cements based on silicate cement include expansive cement, two-component low-exothermic cement, and three-component low-exothermic cement.

[0206] Examples of special cements obtained by changing the ingredients and particle size composition of silicate cement include white silicate cement, cement-based solidifying materials (geocement), ultrafine cement, and high-bicalcium silicate cement.

[0207] Examples of special cements having components different from those of silicate cement include ultra-fast hardening cement, alumina cement, phosphate cement, and air-hardening cement.

[0208] <Liquid>

[0209] The liquid agent is selected according to the type of curable powder, and examples thereof include water, solvents, and mixtures thereof, and water is usually used. The solvent may be used alone or in combination of two or more.

[0210] The ratio of the curable powder to the liquid agent in the cement slurry may be appropriately determined according to the specific gravity of the target slurry or the strength of the solidified body, etc. For example, when the cement slurry is formed in the form of drilling cement slurry using hydraulic cement, the ratio of water to cement (W / C) is preferably 25% by mass or more and 100% by mass or less, and more preferably 30% by mass or more and 80% by mass or less, from the viewpoint of the specific gravity of the slurry and the strength of the solidified body.

[0211] <Optional Ingredients>

[0212] As optional components, a dispersant, a retarder, and a defoaming agent may be contained, and additives other than these may be contained as desired. The optional components may be used alone or in combination of two or more.

[0213] (Dispersant)

[0214] Examples of the dispersant include anionic polymers such as naphthalenesulfonic acid formaldehyde condensates, melaminesulfonic acid formaldehyde condensates, and polycarboxylic acid polymers, among which naphthalenesulfonic acid formaldehyde condensates are preferred. The content of the dispersant is usually 0.05% (BWOC) or more and 2% (BWOC) or less, and preferably 0.2% (BWOC) or more and 1% (BWOC) or less.

[0215] (Delay Agent)

[0216] Examples of the retarder include hydroxycarboxylic acids or salts thereof, monosaccharides, polysaccharides and other sugars, of which sugars are preferred. The content of the retarder is usually 0.005% (BWOC) to 1% (BWOC), preferably 0.02% (BWOC) to 0.3% (BWOC).

[0217] (Defoaming Agent)

[0218] Examples of defoamers include alcohol alkylene oxide adducts, fatty acid alkylene oxide adducts, polypropylene glycol, fatty acid soaps, silicon compounds, etc., among which silicon compounds are preferred. The content of the defoamer is usually 0.0001% (BWOC) or more and 0.1% (BWOC) or less, preferably 0.001% (BWOC) or more and 0.05% (BWOC) or less.

[0219] (additive)

[0220] The cement paste may contain additives such as cement quick-hardening agent, low specific gravity additive, high specific gravity additive, foaming agent, crack reducing agent, bubble agent, AE agent, cement expansion material, cement strength stabilizing material, silica powder, silicon-containing smoke, fly ash, limestone powder, fine aggregate such as crushed sand, coarse aggregate such as crushed stone, hollow spheres, etc., in consideration of the purpose, composition, etc. These additives may be used alone or in combination of two or more.

[0221] [Filling agent for underground treatment]

[0222] The underground treatment filler of the present invention comprises a vinyl alcohol polymer (X) obtained by polymerizing and saponifying a plant-derived vinyl ester monomer (A) and a petroleum-derived vinyl ester monomer (B), wherein the molar ratio of (A) / (B) is 5 / 95 to 90 / 10.

[0223] The underground treatment filler of the present invention contains the above-mentioned PVA (X). The content of PVA (X) is not particularly limited, but is preferably 50 to 100 mass%, more preferably 80 to 100 mass%, and further preferably 90 to 100 mass% relative to the entire underground treatment filler. By making the content of PVA (X) within the above range, there is a tendency for the filling effect to be more excellent.

[0224] The underground processing filler of the present invention enters into the cracks formed during the drilling of oil or shale gas, etc., temporarily plugging the cracks, thereby forming new cracks. As a method of plugging cracks using the underground processing filler of the present invention, the underground processing filler can be made to flow into the cracks to be plugged by the flow of fluid in the mine.

[0225] In addition, the underground treatment filling agent of the present invention temporarily seals the cracks in the ground, but slowly dissolves in water and is removed when or after the recovery of underground resources such as oil and natural gas, so it does not stay in the ground for a long time. Therefore, the underground treatment filling agent of the present invention also has a very small burden on the environment.

[0226] The shape of PVA (X) used in the underground treatment filler is not particularly limited, and may be in the form of pellets, granules, powder, etc. The pelletization can be carried out by a common method such as extrusion molding, and a plasticizer such as polyethylene glycol described below may be appropriately added.

[0227] When a powdery substance is used as PVA(X) for underground treatment filler, the average particle size is preferably 10 to 5000 μm, more preferably 50 to 4000 μm, further preferably 100 to 3500 μm, and particularly preferably 500 to 3000 μm.

[0228] By making the average particle size of PVA (X) within the above range, the PVA-based resin will not scatter and will be easier to handle. In addition, even in the case where, for example, the PVA (X) is subsequently modified, there is a tendency for the reaction to become uniform and better. It should be noted that the average particle size refers to the diameter at which the cumulative value (cumulative distribution) reaches 50% of the volume distribution of each particle size measured by laser diffraction. Specifically, the laser diffraction scattering method can utilize, for example, a laser diffraction particle size distribution measuring device (SALD-2300: manufactured by Shimadzu Corporation), using a 0.2% sodium hexametaphosphate aqueous solution as a dispersion medium and measuring on a volume basis.

[0229] The underground treatment filler of the present invention may further contain additives. Examples of the additives include fillers, plasticizers, starch, etc. The additives may be used alone or in combination of two or more.

[0230] The filler can be mixed with PVA (X) to further improve the mechanical properties or adjust the water solubility rate. The amount of the filler added is appropriately selected according to the purpose, for example, preferably less than 50% by mass of the entire filler, more preferably less than 30% by mass, and further preferably less than 5% by mass.

[0231] The specific gravity of the filler for underground treatment is preferably close to the specific gravity of the fluid used in underground treatment, so that it can be more evenly distributed in the system by means of, for example, pump power. From the viewpoint of adjusting the specific gravity of the filler for underground treatment, an extender can be added to PVA (X). The specific gravity of PVA (X) can be increased by adding an extender. As examples of extenders, salts of natural minerals, inorganic substances and organic substances can be listed, which can be, for example, a compound formed by one or more metal ions selected from calcium, magnesium, silicon, barium, copper, zinc, and manganese and one or more counterions selected from fluoride, chloride, bromide, carbonate, hydroxide, formates, acetates, nitrates, sulfates, and phosphates. Among them, calcium carbonate, calcium chloride, zinc oxide, etc. are preferred.

[0232] In order to improve the fluid properties of the underground treatment filler, the underground treatment filler may further include a plasticizer on the basis of PVA (X). In other words, PVA (X) may be added or mixed with a plasticizer. At this time, in order to uniformly add the plasticizer to PVA (X), a method of spraying the plasticizer on the surface of PVA (X) may be used. By adding a plasticizer, the generation of fine powder can sometimes be further suppressed. Plasticizers can use known substances, and suitable plasticizers include water, glycerol, polyglycerol, ethylene glycol, polyethylene glycol, ethanol acetamide, ethanol formamide, triethanolamine acetate, glycerol, trimethylolpropane, neopentyl glycol, etc. They may be used alone or in combination of two or more. Substances that are solid or crystalline at room temperature, such as trimethylolpropane, can be used for spraying by dissolving in water or other liquids. The content of the plasticizer is preferably 40% by mass or less, more preferably 30% by mass or less, and further preferably 20% by mass or less, based on the mass of PVA(X) (100% by mass).

[0233] As a suitable embodiment, there can be cited a filler for underground treatment comprising a composition of PVA (X) and an additive, wherein the additive comprises a filler and a plasticizer. As the blending ratio of each component in the filler for underground treatment, it is preferred that: PVA (X) is 60 to 94% by mass, the filler is 5 to 40% by mass, and the plasticizer is 1 to 15% by mass.

[0234] In addition, in the underground treatment filler of the present invention, starch can be mixed with PVA (X). When PVA (X) is set to 100 mass %, the amount of starch added is preferably 10 to 90 mass %, more preferably 30 mass % or more. Examples of starch include natural products, synthetic products, physically modified or chemically modified starch, etc.

[0235] The underground treatment filling material of the present invention may further contain additives such as a chelating agent, a pH adjuster, an oxidant, a mud loss material, an antioxidant, a rust preventive, clay, an iron agent, a reducing agent, and an oxygen remover as needed.

[0236] [Multilayer structure]

[0237] The multilayer structure of the present invention comprises a layer (C) containing a vinyl alcohol polymer (X) obtained by polymerizing and saponifying a plant-derived vinyl ester monomer (A) and a petroleum-derived vinyl ester monomer (B), and a layer (D) containing a resin.

[0238] The aforementioned resin is at least one resin selected from polyolefin resin, polyester resin, polyamide resin, polyvinyl chloride (PVC) resin, ABS resin, polylactic acid (PLA) resin, polybutylene succinate (PBS) resin, polyhydroxyalkanoate (PHA) resin, polyhydroxybutyrate / hydroxyhexanoate (PHBH) resin, starch and cellulose.

[0239] [Layer (C)]

[0240] The layer (C) constituting the multilayer structure of the present invention contains the above-mentioned PVA (X).

[0241] The content of the PVA (X) in layer (C) is preferably 50% by mass or more, more preferably 80% by mass or more, and further preferably 95% by mass or more. In addition, in layer (C), the mass ratio of the vinyl alcohol polymer to the total polymer components (vinyl alcohol polymer / total polymer components) is preferably 0.9 or more, and it is more suitable that the polymer components contained in layer (C) substantially only contain the PVA (X). In the case of substantially containing only the PVA (X), the content of components other than PVA (X) is preferably less than 0.5% by mass, more preferably less than 0.1% by mass, and further preferably less than 0.01% by mass.

[0242] [Layer (D)]

[0243] Layer (D) is a substrate containing a resin. Examples of the resin include polyolefin resins, polyester resins, polyamide resins, polyvinyl chloride (PVC) resins, ABS resins, polylactic acid (PLA) resins, polybutylene succinate (PBS) resins, polyhydroxyalkanoate (PHA) resins, polyhydroxybutyrate / hydroxyhexanoate (PHBH) resins, starch, and cellulose. The resins may be used alone or in combination of two or more. The thickness of layer (D) (final thickness when stretched) is preferably 5 to 100 μm.

[0244] Examples of polyolefin resins include polyethylene, polypropylene, copolymerized polypropylene, ethylene-vinyl acetate copolymers, and ethylene-(meth)acrylate copolymers. Examples of polyethylene include high-density polyethylene (HDPE), low-density polyethylene (LDPE), linear low-density polyethylene (LLDPE), and ultra-low-density polyethylene (VLDPE). Among them, polyethylene and polypropylene are preferred. It should be noted that, in this specification, "(meth)acrylic acid" is a general term for acrylic acid and methacrylic acid. The same is true for "(meth)acrylate" and the like.

[0245] Examples of the polyester resin include polyethylene terephthalate (hereinafter sometimes abbreviated as "PET"), polyethylene naphthalate, polybutylene terephthalate, polyethylene terephthalate / ethylene isophthalate, etc. Among them, polyethylene terephthalate (PET) is preferred.

[0246] Examples of the polyamide resin include homopolymers such as polycaprolactam (nylon-6), polyundecanoic acid amide (nylon-11), polylaurolactam (nylon-12), polyhexamethylenediamine adipamide (nylon-6,6), and polyhexamethylenediamine sebacamide (nylon-6,12); and copolymers such as aromatic nylons, wherein the aromatic nylons are caprolactam / laurolactam copolymers (nylon-6 / 12), caprolactam / aminoundecanoic acid polymers (nylon-6 / 11), caprolactam / ω-aminononanoic acid polymers (nylon-6,9), caprolactam / hexamethylenediamine adipate copolymers (nylon-6 / 6,6), caprolactam / hexamethylenediamine adipate / hexamethylenediamine sebacate copolymers (nylon-6 / 6,6 / 6,12), polymers of adipic acid and meta-xylylenediamine, and polymers of hexamethylenediamine and isophthalic acid or terephthalic acid. Among them, polycaprolactam (nylon-6) and polyhexamethylene adipamide (nylon-6,6) are preferred.

[0247] As the polyvinyl chloride resin, for example, a homopolymer of vinyl chloride or a copolymer of vinyl chloride and other monomers can be used. As other monomers, for example, α-olefins such as ethylene, propylene, and butene; dienes such as butadiene and isoprene; vinyl esters such as vinyl acetate and vinyl propionate; vinyl ethers such as butyl vinyl ether and cetyl vinyl ether; (meth)acrylates such as methyl (meth)acrylate, ethyl (meth)acrylate, butyl acrylate, phenyl methacrylate, and hydroxyethyl (meth)acrylate; aromatic vinyls such as styrene and α-methylstyrene; halogenated vinyls such as vinylidene chloride and vinylidene fluoride; N-substituted maleimides such as N-phenylmaleimide and N-cyclohexylmaleimide; (meth)acrylic acid, maleic anhydride, acrylonitrile, polyorganosiloxane, etc. These monomers can be used alone or in combination. The amount of the monomer copolymerizable with the vinyl chloride monomer is preferably in the range of 0 to 50 parts by mass based on 100 parts by mass of the total of vinyl chloride and the monomer copolymerizable with the vinyl chloride monomer.

[0248] Examples of ABS (Acrylonitrile Butadiene Styrene) resins include resins containing acrylonitrile, butadiene, and styrene as structural units, such as flame-retardant ABS resins, reinforced ABS resins reinforced with glass fiber, phenylmaleimide-based ABS resins, etc. Examples of ABS resins include α-methylstyrene-based ABS resins obtained by replacing styrene with α-methylstyrene, ASA (Acrylonitrile-Styrene-Acrylate resin) resins obtained by replacing butadiene with acrylic rubber, ACS (Chlorinated-polyethylene-Acrylonitrile-Styrene resin) resins obtained by replacing butadiene with chlorinated polyethylene, and AES (Acrylonitrile-Ethylene-Styreneresin) resins obtained by replacing butadiene with EPDM (ethylene propylene diene terpolymer).

[0249] As polylactic acid (PLA) resin, there can be cited resins obtained by polymerization containing lactic acid monomer as the main component, which contain more than 50 mol% of structural units derived from lactic acid. As polylactic acid resin, there can be cited, for example, poly (L-lactic acid) whose structural unit is L-lactic acid, poly (D-lactic acid) whose structural unit is D-lactic acid, poly (DL-lactic acid) whose structural unit is L-lactic acid and D-lactic acid, and polymers whose mixtures thereof are the main components.

[0250] The polybutylene succinate (PBS) resin contains 1,4-butanediol and succinic acid in the structural unit, and a copolymer in which 3-alkoxy-1,2-propylene glycol is copolymerized with 1,4-butanediol and succinic acid can also be used. In the 3-alkoxy-1,2-propylene glycol used in the above copolymer, the number of carbon atoms of the alkoxy group is preferably 1 to 10, more preferably 1 to 8. The PBS resin can use a plant-derived PBS resin.

[0251] Examples of the polyhydroxyalkanoate (PHA) resin include poly(3-hydroxyvalerate), poly(3-hydroxybutyrate), poly(3-hydroxypropionate), poly(4-hydroxybutyrate), poly(3-hydroxyoctanoate), and poly(3-hydroxydecanoate).

[0252] The polyhydroxybutyrate / hydroxyhexanoate (PHBH) resin is a copolymer of 3-hydroxybutyrate and 3-hydroxyhexanoate (3-hydroxybutyrate-co-3-hydroxyhexanoate polymer). In the copolymer, the amount of 3-hydroxyhexanoate may be 1 to 20 mol% in all structural units.

[0253] Examples of starch include corn starch, potato starch, sweet potato starch, wheat starch, cassava starch, sago starch, tapioca starch, sorghum starch, rice starch, bean starch, kudzu starch, bracken starch, lotus root starch, water chestnut starch, and other raw starches (self-modified starches): α-starch, fractionated amylose, wet heat treated starch, thermochemically modified starch, and other physically modified starches: hydrolyzed dextrin, enzymatically decomposed dextrin, amylose, and other enzymatically modified starches; acid-treated starch, hypochlorous acid-oxidized starch, and other oxidized starches; chemically decomposed modified starches such as dialdehyde starch; chemically modified starch derivatives such as esterified starch, etherified starch, cationized starch, and cross-linked starch; alkyl starch, hydroxyalkyl starch, hydroxyalkyl alkyl starch, and the like. Examples of alkyl starch include methyl starch, ethyl starch, and propyl starch, and the like. Examples of hydroxyalkyl starch include hydroxymethyl starch, hydroxyethyl starch, and hydroxypropyl starch, and the like. Examples of hydroxyalkyl alkyl starch include hydroxymethyl methyl starch, hydroxyethyl methyl starch, hydroxypropyl methyl starch, etc. Examples of esterified starch among chemically modified starch derivatives include acetic acid esterified starch, succinic acid esterified starch, nitric acid esterified starch, phosphate esterified starch, urea phosphate esterified starch, xanthate esterified starch, acetoacetate esterified starch, carbamate esterified starch, etc. Examples of etherified starch include allyl etherified starch, methyl etherified starch, carboxyl etherified starch, carboxymethyl etherified starch, hydroxyethyl etherified starch, hydroxypropyl etherified starch, etc. Examples of cationic starch include reactants of starch and 2-diethylamino ethyl chloride, reactants of starch and 2,3-epoxypropyltrimethylammonium chloride, etc. Examples of cross-linked starch include formaldehyde cross-linked starch, epichlorohydrin cross-linked starch, phosphate cross-linked starch, acrolein cross-linked starch, etc.

[0254] As cellulose, alkyl cellulose, hydroxyalkyl cellulose, cellulose acetate, etc. can be listed. As alkyl cellulose, methyl cellulose, etc. can be listed. The content of methoxy in methyl cellulose is preferably 26.0 to 33.0% by mass, more preferably 27.5 to 31.5% by mass. The content of methoxy in methyl cellulose can be measured according to the analytical method related to methyl cellulose in the 17th edition of the revised Japanese Pharmacopoeia. As hydroxyalkyl cellulose, hydroxypropyl cellulose, etc. can be listed. The content of hydroxypropoxy in hydroxypropyl cellulose is preferably 53.4 to 80.5% by mass, more preferably 60.0 to 70.0% by mass. The content of hydroxypropoxy in hydroxypropyl cellulose can be measured according to the analytical method related to hydroxypropyl cellulose in the 17th edition of the revised Japanese Pharmacopoeia.

[0255] The oxygen permeability of the multilayer structure of the present invention is preferably 150 cc / m2 ·day·atm or less, more suitable for 100cc / m 2 ·day·atm or less. In the present invention, the oxygen permeability of the multilayer structure is determined by the method described in Examples.

[0256] Each layer in the multilayer structure of the present invention may contain an inorganic layered compound for the purpose of improving gas barrier properties, increasing strength or improving handling properties. Examples of the inorganic layered compound include micas, talc, montmorillonite, kaolinite, vermiculite, etc., which may be naturally occurring substances or synthetic substances.

[0257] Each layer in the multilayer structure of the present invention may contain a crosslinking agent for the purpose of improving water resistance. Examples of the crosslinking agent include epoxy compounds, isocyanate compounds, aldehyde compounds, titanium compounds, silica compounds, aluminum compounds, zirconium compounds, boron compounds, etc. Among them, silica compounds such as colloidal silica and alkyl silicates are preferred.

[0258] The method for producing the multilayer structure of the present invention is not particularly limited, and is preferably a method having the following steps: a step of preparing an aqueous solution containing the aforementioned vinyl alcohol polymer (X) (hereinafter sometimes abbreviated as PVA (X) aqueous solution) to obtain a coating agent; and a step of applying the coating agent to the surface of a substrate containing at least one resin selected from polyolefin resins, polyester resins, and polyamide resins. It should be noted that, as described later, as a preferred embodiment of the present invention, in the case where there is a layer such as an adhesive component layer between layer (C) and layer (D), the coating agent can be applied to the layer such as the adhesive component layer formed on the substrate to produce the multilayer structure. In this application, even in such a case, it is sometimes expressed as "applying the coating agent to the surface of the substrate".

[0259] As the aforementioned substrate, a film comprising the aforementioned resin can be listed. In a certain suitable embodiment, as the aforementioned substrate, a film comprising a polyolefin resin (hereinafter also referred to as a polyolefin film), a film comprising a polyester resin (hereinafter also referred to as a polyester film), and a film comprising a polyamide resin (hereinafter also referred to as a polyamide film) can be listed. In other suitable embodiments, as the aforementioned substrate, a film comprising a polyvinyl chloride (PVC) resin (hereinafter also referred to as a polyvinyl chloride film), a film comprising an ABS resin (hereinafter also referred to as an ABS film), a film comprising a polylactic acid (PLA) resin (hereinafter also referred to as a polylactic acid film), a film comprising polybutylene succinate (PBS) resin (hereinafter also referred to as a polybutylene succinate film), a film comprising a polyhydroxyalkanoate (PHA) resin (hereinafter also referred to as a polyhydroxyalkanoate film), a film comprising polyhydroxybutyrate / hydroxyhexanoate (PHBH) resin (hereinafter also referred to as a polyhydroxybutyrate / hydroxyhexanoate film), a film comprising starch (hereinafter also referred to as a starch film) and a film comprising cellulose (hereinafter also referred to as a cellulose film). The substrate forms a layer (D).

[0260] The content of the PVA (X) in the PVA (X) aqueous solution is not particularly limited, and is preferably 5 to 50% by mass. If it is within the above range, the drying burden is reduced or the viscosity of the aqueous solution is moderate, so the coating property becomes better. Layer (C) is formed by applying a coating agent containing the PVA (X) aqueous solution to the surface of the substrate and then drying it. The evaporation rate during the drying process is preferably 2 to 2000 g / m 2 ·min, more suitable for 50~500g / m 2 ·min.

[0261] The aforementioned PVA (X) aqueous solution and coating agent may contain a surfactant, a leveling agent, etc. In addition, from the viewpoint of coating properties, the aforementioned PVA (X) aqueous solution and coating agent may contain lower aliphatic alcohols such as methanol, ethanol, and isopropanol. In this case, the content of the lower aliphatic alcohol contained in the aforementioned PVA (X) aqueous solution is suitable to be 100 parts by mass or less relative to 100 parts by mass of water, more preferably 50 parts by mass or less, and further suitable to be 20 parts by mass or less. From the viewpoint of the working environment, the liquid medium contained in the aforementioned PVA (X) aqueous solution is preferably only water. In addition, the aforementioned PVA (X) aqueous solution may contain a mildewproofing agent, a preservative, etc. The temperature during coating of the aforementioned PVA (X) aqueous solution is preferably 20 to 80°C. The coating method is suitable for using a gravure roll coating method, a reverse gravure coating method, a reverse roll coating method, and a wire rod coating method. The substrate or the resulting multilayer structure before applying the coating agent may be stretched or heat treated. In this case, considering workability, a method is preferably used in which a coating agent is applied to the substrate after the substrate is stretched in one step, and then the substrate is stretched in two steps, and heat-treated during or after the two-step stretching.

[0262] The aforementioned heat treatment is carried out in air or the like. The heat treatment temperature can be adjusted according to the type of the aforementioned substrate, and is generally 140°C to 170°C in the case of polyolefin films. In the case of polyester films and polyamide films, the heat treatment temperature is 140°C to 240°C. In the case of polyvinyl chloride films, the heat treatment temperature is 140°C to 200°C. In the case of ABS films, the heat treatment temperature is 140°C to 170°C. In the case of polylactic acid films, the heat treatment temperature is 140°C to 240°C. In the case of polybutylene succinate films, the heat treatment temperature is 140°C to 240°C. In the case of polyhydroxyalkanoate films, the heat treatment temperature is 140°C to 240°C. In the case of polyhydroxybutyrate / hydroxyhexanoate films, the heat treatment temperature is 140°C to 240°C. In the case of starch films, the heat treatment temperature is 140°C to 240°C. In the case of cellulose films, the heat treatment temperature is 140°C to 240°C. When the heat treatment of the layer (C) is performed, it is usually performed simultaneously with the heat treatment of the layer (D) which is the substrate.

[0263] The thickness of layer (C) (when stretched, the final thickness after stretching) is preferably 0.1 to 20 μm, more preferably 0.1 to 9 μm. In addition, the multilayer structure may include two or more layers (C). The PVA (X) contained in the two or more layers (C) may be the same or different. In the case where the multilayer structure includes two or more layers (C), the thickness of the aforementioned layer (C) represents the thickness of one layer (C).

[0264] The thickness ratio of layer (C) to layer (D) in the multilayer structure ((C) / (D)) is preferably 0.9 or less, more preferably 0.5 or less. When the multilayer structure includes two or more layers (C), the thickness ratio of layer (D) to each layer (C) is indicated.

[0265] For the purpose of improving adhesion, an adhesive component layer may be formed between layer (C) and layer (D). Examples of the adhesive component include anchor coating agents, etc. The adhesive component layer may be formed by applying the adhesive component to the surface of the substrate before applying the coating agent, etc.

[0266] In the multilayer structure of the present invention, a heat seal resin layer may be further formed on the surface of layer (C) that is not in contact with layer (D). The heat seal resin layer is usually formed by extrusion lamination or dry lamination. As the heat seal resin, polyethylene resins such as HDPE, LDPE, and LLDPE, polypropylene resins, ethylene-vinyl acetate copolymers, ethylene α-olefin random copolymers, ionomer resins, etc. can be used.

[0267] [Packaging materials]

[0268] A packaging material including the multilayer structure of the present invention is also a suitable embodiment of the present invention. Since the packaging material includes the multilayer structure of the present invention, it has excellent oxygen barrier properties.

[0269] The packaging material is used for packaging, for example, food, beverages, pesticides, medicines and other chemical drugs, medical devices, industrial materials such as machine parts and precision materials, clothing, etc. In particular, the packaging material is suitable for applications requiring barrier properties against oxygen and applications where the interior of the packaging material is replaced with various functional gases.

[0270] Examples of the form of the packaging material include a vertical pouch fill seal bag, a vacuum packaging bag, a spouted soft bag, a laminated tube container, and a container cover.

[0271] [Paper coating agent]

[0272] The paper coating agent of the present invention comprises a vinyl alcohol polymer (X) obtained by polymerizing and saponifying a plant-derived vinyl ester monomer (A) and a petroleum-derived vinyl ester monomer (B), wherein the molar ratio of (A) / (B) is 5 / 95 to 100 / 0.

[0273] The substrate to which the paper coating agent of the present invention is applied is not particularly limited, and examples thereof include paper and substrates containing resins, etc. As the paper coating agent, the paper coating agent of the present invention may be used as it is, or may be used by further adding other components.

[0274] As the above-mentioned other components, the components mentioned above as other components other than the vinyl alcohol polymer (X) and water can be listed. In addition, as the above-mentioned other components, water-resistant agents such as glyoxal, urea resin, melamine resin, polyvalent metal salt, water-soluble polyamide resin, etc.; pH adjusters such as ammonia, caustic soda, sodium carbonate, phosphoric acid, etc.; mold release agents; colorants such as pigments; various modified PVAs such as unmodified PVA, carboxyl-modified PVA, sulfonic acid-modified PVA, acrylamide-modified PVA, cationic group-modified PVA, and long-chain alkyl-modified PVA that do not belong to the vinyl alcohol polymer (X); casein, raw starch (wheat, corn, rice, potato, sweet potato, cassava, etc.); , sago coconut), raw starch decomposition products (dextrin, etc.), starch derivatives (oxidized starch, etherified starch, esterified starch, cationized starch, etc.), seaweed polysaccharides (sodium alginate, carrageenan, agar (agarose, agar gum), furcellaran, etc.), water-soluble cellulose derivatives (carboxyalkyl cellulose, alkyl cellulose, hydroxyalkyl cellulose, etc.) and other water-soluble polymers; synthetic resin emulsions such as styrene-butadiene copolymer latex, polyacrylate emulsion, vinyl acetate-ethylene copolymer emulsion, vinyl acetate-acrylate copolymer emulsion, etc. The concentration of the vinyl alcohol polymer (X) in the paper coating agent is arbitrarily selected depending on the coating amount (increase in dry mass of paper generated by coating), the device used for coating, the operating conditions, etc., and is preferably 1.0 to 30% by mass, and more preferably 2.0 to 25.0% by mass.

[0275] As a method for applying the paper coating agent of the present invention to paper, known methods can be listed, such as a method of coating one or both sides of the paper using a sizing machine, a coating roll, a SYM-SIZER, a rod coater, a curtain coater, etc.; or a method of impregnating the paper with a coating liquid (paper coating agent). The coated paper can be dried by known methods, such as hot air, infrared rays, a heating cylinder, or a combination thereof. The dried coated paper can be further improved in barrier properties by humidity adjustment and calendering. As calendering treatment conditions, the roller temperature is preferably room temperature to 100°C, and the roller line pressure is preferably 20 to 300 kg / cm.

[0276] As another embodiment, coated paper obtained by coating the paper coating agent of the present invention on paper can be cited. The coated paper obtained using the paper coating agent of the present invention can be used as a release paper base paper, oil-resistant paper, air-barrier paper, thermal paper, inkjet paper, pressure-sensitive paper, etc. Among them, release paper base paper or oil-resistant paper is preferred. That is, as a certain embodiment, the above-mentioned coated paper as a release paper base paper or oil-resistant paper can be cited.

[0277] The release paper base paper has a filling layer (barrier layer) formed of a paper coating liquid on a substrate (paper). Examples of the substrate (paper) include paperboards such as abaca paperboard, white paperboard, and liner; general high-quality paper, medium-quality paper, gravure paper and other printing papers. The release paper has a release layer laminated on the filling layer of the release paper base paper. The release layer is preferably composed of a silicone resin. Examples of the silicone resin include well-known silicone resins such as solvent-based silicones, solvent-free silicones, and emulsion-based silicones. The coating amount in the release paper base paper (the increase in the dry mass of the paper generated by coating) is not particularly limited, and is, for example, 0.1 to 5.0 g / m 2 , preferably 0.1 to 2.5 g / m 2 .

[0278] Oil-resistant paper has an oil-resistant layer formed by a paper coating liquid on a substrate (paper). Examples of the substrate (paper) include abaca paperboard, white paperboard, liner paper, and other paperboards; general high-quality paper, medium-quality paper, gravure paper, and other printing papers; kraft paper, glass paper, parchment paper, and the like. The coating amount (the increase in the dry mass of the paper generated by coating) in oil-resistant paper is not particularly limited, and is, for example, 0.1 to 20 g / m 2 .

[0279] The paper coating agent (paper coating liquid) of the present invention may contain other ingredients in addition to PVA (X) and water, provided that the effect of the present invention is not hindered. As the above-mentioned other ingredients, resins, organic solvents, plasticizers, cross-linking agents, surfactants, anti-precipitation agents, thickeners, fluidity improvers, preservatives, adhesion improvers, antioxidants, penetrants, defoamers, fillers, wetting agents, colorants, binders, water-retaining agents, fillers, sugars such as starch and its derivatives, latex and other additives other than PVA (X) can be listed. They can be used alone or in combination of two or more. The content of the above-mentioned other ingredients in the paper coating agent of the present invention is preferably less than 10% by mass, and sometimes preferably less than 5% by mass, less than 2% by mass, less than 1% by mass or less than 0.5% by mass.

[0280] [Seed coating composition]

[0281] The seed coating composition of the present invention comprises a vinyl alcohol polymer (X) (hereinafter sometimes abbreviated as PVA(X)) obtained by polymerizing and saponifying a plant-derived vinyl ester monomer (A) and a petroleum-derived vinyl ester monomer (B), wherein the molar ratio of (A) / (B) is 5 / 95 to 100 / 0.

[0282] (pesticide)

[0283] The seed coating composition may further comprise one or more hydrophobic pesticides. In the present invention, "pesticide" is used broadly to refer to insecticides, fungicides, nematocides, and similar agents that prevent or reduce damage to seeds caused by living organisms.

[0284] In the context of the present invention, a "hydrophobic" pesticide additive is one that is insoluble in water (eg, when no surfactant is used) or is capable of being stably dispersed in water.

[0285] Such hydrophobic pesticides are generally known to those skilled in the art and are generally commercially available. Examples of commercially available hydrophobic pesticides include Acceleron, which is a mixture of a fungicide and an insecticide. TM Set (including pyraclostrobin, fluopicolide, metalaxyl and imidacloprid), etc.

[0286] Examples of suitable fungicides include pyraclostrobin, fluopicolide, ipconazole, trifloxystrobin, metalaxyl (Metalaxyl 265 ST), fluclostrobin (fluclostrobin 4L ST), thiabendazole (thiabendazole 4L ST), trichlorfonazole, tefluthrin, and combinations thereof.

[0287] Examples of suitable insecticides include clothianidin, imidacloprid, SENATOR (registered trademark) 600ST (NufarmUS), tefluthrin, terbufos, cypermethrin, thiodicarb, lindane, furathiocarb, acephate, and combinations thereof.

[0288] Typically, hydrophobic pesticides are used in small amounts (in order to use an "effective amount" to achieve the desired pesticide effect) in accordance with the dosage recommended by the manufacturer of such pesticides.

[0289] (Aqueous coating composition)

[0290] In a certain suitable embodiment, the seed coating composition is an aqueous coating composition. The aqueous coating composition comprises water as a main carrier medium.

[0291] The lower limit of the content of PVA (X) in the coating composition is preferably 0.5% by mass, more preferably 1.0% by mass, and further preferably 2.0% by mass, based on the total mass of the coating composition. In addition, the upper limit of the content of PVA (X) in the coating composition is preferably 10% by mass, more preferably 8% by mass, and further preferably 6% by mass, based on the total mass of the coating composition.

[0292] According to the optional components as described below, the lower limit of the solid content of the aqueous coating composition of the present invention is preferably 1% by mass, more preferably 2% by mass, and further preferably 5% by mass based on the total mass of the aqueous coating composition. In addition, the upper limit of the solid content of the aqueous coating composition of the present invention is preferably 25% by mass, more preferably 20% by mass, based on the total mass of the aqueous coating composition.

[0293] Alternatively, the aqueous coating composition may be provided as a concentrate that can be diluted with water for application to seeds.

[0294] Depending on the PVA (X) and other optional ingredients, the aqueous coating composition can be in the form of a solution, dispersion, emulsion or suspension as understood by those skilled in the art. For example, several ingredients may be present in a solution, while other ingredients may be dispersed, emulsified and / or suspended. In this case, the ingredients of the aqueous coating composition are preferably substantially uniformly dispersed in the aqueous coating composition before application. Therefore, the aqueous coating composition is preferably a stable solution, emulsion and / or dispersion; alternatively, a solution, emulsion, dispersion and / or suspension in which the ingredients can be easily uniformly dispersed by existing means such as stirring with or without gentle heating.

[0295] (Optional Ingredients)

[0296] In the seed coating composition of the present invention, on the basis of containing PVA (X), other optional ingredients may also be included. As other optional ingredients, other polymers, plasticizers, talc, wax, pigments and debonding agents other than PVA (X) may be listed. One of them may be used alone, or two or more may be used in combination. For example, other polymers other than PVA (X) may be blended with PVA (X) to improve coating properties. As other polymers other than PVA (X), for example, polyvinyl pyrrolidone, starch and high molecular weight polyethylene glycol may be listed. In addition, plasticizers, talc, wax, pigments and debonding agents may be added to seed coating solutions, emulsions or suspensions as needed.

[0297] (Application of aqueous coating composition)

[0298] Methods for applying the aqueous coating composition to seeds are well known to those skilled in the art. Existing methods include, for example, mixing, spraying, or combinations thereof. Various coating machines such as spin coaters, drum coaters, fluidized beds, etc. using various coating techniques are commercially available. Seeds can be coated by intermittent or continuous coating processes.

[0299] The seeds are preferably substantially uniformly coated with a thin film of the coating composition.

[0300] (covering seeds)

[0301] Examples of seeds to be treated with the seed coating composition of the present invention include wheat, barley, rye, sorghum, apples, peaches, cherries, strawberries, blackberries, sugar beets, beets, lentils, peas, soybeans, peppers, olives, sunflowers, coconut oil plants, cocoa beans, tuna, sea cucumbers (cumber), melons, flax, hemp, oranges, lemons, grapefruits, tangerines, lettuce, asparagus, cabbage, carrots, onions, tomatoes, red peppers, avocados, flowers, broadleaf trees, corn, potatoes, bulbs, rice, tobacco, nuts, coffee, and sugarcane.

[0302] [Water-based emulsion]

[0303] The aqueous emulsion of the present invention comprises a dispersant and a dispersoid, wherein the dispersoid comprises a polymer (Y1) containing an ethylenically unsaturated monomer unit, and the dispersant comprises a vinyl alcohol polymer (X) obtained by polymerizing and saponifying a vinyl ester monomer (A) derived from a plant and a vinyl ester monomer (B) derived from petroleum, wherein the molar ratio of (A) / (B) is 5 / 95 to 100 / 0.

[0304] The aqueous emulsion of the present invention is an aqueous emulsion containing the above-mentioned PVA (X) as a dispersant and a polymer (Y1) containing ethylenically unsaturated monomer units as a dispersoid. The ratio of PVA (X) to the polymer (Y1) containing ethylenically unsaturated monomer units is not particularly limited, and the mass ratio ((X) / (Y1)) based on the solid content is preferably 2 / 98 to 20 / 80, and more preferably 5 / 95 to 15 / 85. By making the mass ratio within the above range, there is a tendency that the viscosity stability of the obtained aqueous emulsion becomes better and the water resistance of the obtained coating becomes better.

[0305] The solid content in the aqueous emulsion of the present invention is not particularly limited, but is preferably 30% by mass or more and 60% by mass or less, and more preferably 35% by mass or more and 55% by mass or less.

[0306] [Ethylenically unsaturated monomer unit]

[0307] Examples of the ethylenically unsaturated monomers that are the materials of the polymer (Y1) containing ethylenically unsaturated monomer units include olefin monomers such as ethylene, propylene, and isobutylene; halogenated olefin monomers such as vinyl chloride, vinyl fluoride, vinylidene chloride, and vinylidene fluoride; vinyl ester monomers such as vinyl formate, vinyl acetate, vinyl propionate, and vinyl versatate; (meth)acrylic acid, methyl (meth)acrylate, ethyl (meth)acrylate, butyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, dodecyl (meth)acrylate, (meth)acrylate, (Meth)acrylate monomers such as 2-hydroxyethyl (meth)acrylate; dimethylaminoethyl (meth)acrylate and its quaternary products; (meth)acrylamide monomers such as (meth)acrylamide, N-hydroxymethyl (meth)acrylamide, N,N-dimethyl (meth)acrylamide, (meth)acrylamide-2-methylpropanesulfonic acid and its sodium salt; styrene monomers such as styrene, α-methylstyrene, p-styrenesulfonic acid and their sodium salts and potassium salts; diene monomers such as butadiene, isoprene, chloroprene; N-vinylpyrrolidone, etc. These can be used alone or in combination of two or more.

[0308] As the polymer (Y1) containing ethylenically unsaturated monomer units, it is preferred that the polymer has a specific unit derived from at least one selected from vinyl ester monomers, (meth) acrylate monomers, styrene monomers and diene monomers. As the content of the above-mentioned specific unit, relative to all monomer units of the polymer, it is suitable to be 70% by mass or more, more suitable to be 75% by mass or more, further suitable to be 80% by mass or more, and particularly suitable to be 90% by mass or more. If the content of the specific unit is less than 70% by mass, there is a tendency that the emulsion polymerization stability of the aqueous emulsion is insufficient.

[0309] Furthermore, among the above-mentioned specific units, vinyl ester monomers are particularly preferred, and vinyl acetate is most preferred. That is, the content of vinyl ester monomer units is preferably 70% by mass or more, more preferably 70% by mass or more, and even more preferably 90% by mass or more, relative to all monomer units of the polymer.

[0310] [Method for producing aqueous emulsion]

[0311] As an example of a method for producing the aqueous emulsion of the present invention, there can be mentioned a method of emulsion polymerization of the above-mentioned ethylenically unsaturated monomer using a polymerization initiator in the presence of PVA (X). The aqueous emulsion obtained in this way does not generate aggregates and has excellent water resistance.

[0312] The dispersion medium in the above-mentioned emulsion polymerization is preferably an aqueous medium with water as the main component. The aqueous medium with water as the main component may contain a water-soluble organic solvent (alcohols, ketones, etc.) that can be soluble in water in any proportion. Here, "aqueous medium with water as the main component" refers to a dispersion medium containing 50% by mass or more of water. From the viewpoint of cost and environmental burden, the dispersion medium is preferably an aqueous medium containing 90% by mass or more of water, more preferably water.

[0313] In the above method, when PVA (X) is added to the polymerization system as a dispersion stabilizer for emulsion polymerization, the feeding method and the adding method are not particularly limited. Examples include: a method of adding a dispersion stabilizer for emulsion polymerization to the polymerization system at the initial stage; and a method of adding continuously during the emulsion polymerization. Among them, from the viewpoint of increasing the grafting rate of PVA (X) on the ethylenically unsaturated monomer, a method of adding a dispersion stabilizer for emulsion polymerization to the polymerization system at the initial stage is preferred. At this time, it is preferred to add PVA (X) to cold water or pre-heated warm water, and to heat to 80 to 90°C and stir in order to evenly disperse the PVA (X).

[0314] The content of PVA (X) as a dispersion stabilizer for emulsion polymerization during emulsion polymerization is not particularly limited, and is preferably 0.2 to 40 parts by mass, more preferably 0.3 to 20 parts by mass, and further preferably 0.5 to 15 parts by mass, relative to 100 parts by mass of the ethylenically unsaturated monomer. When the amount of PVA (X) blended is less than 0.2 parts by mass, there is a tendency for the dispersed particles of the aqueous emulsion to aggregate or for the polymerization stability to decrease. On the other hand, when the amount of PVA (X) blended exceeds 40 parts by mass, there is a tendency for the viscosity of the polymerization system to become too high, the emulsion polymerization will not be uniformly performed, or the heat of polymerization will not be sufficiently removed.

[0315] In the emulsion polymerization, as the polymerization initiator, a water-soluble single initiator or a water-soluble redox initiator commonly used in emulsion polymerization can be used. These initiators can be used alone or in combination of two or more. Among them, redox initiators are preferred.

[0316] Examples of the water-soluble single initiator include azo initiators, hydrogen peroxide, peroxides such as persulfates (potassium, sodium or ammonium salts), etc. Examples of the azo initiator include 2,2'-azobisisobutyronitrile, 2,2'-azobis(2,4-dimethylvaleronitrile), and 2,2'-azobis(4-methoxy-2,4-dimethylvaleronitrile).

[0317] As a redox initiator, a substance obtained by combining an oxidizing agent and a reducing agent can be used. As the oxidizing agent, peroxide is preferred. As the reducing agent, metal ions, reducing compounds, etc. can be listed. As a combination of an oxidizing agent and a reducing agent, a combination of peroxide and metal ions, a combination of peroxide and reducing compounds, and a combination of peroxide and metal ions and reducing compounds can be listed. As peroxides, hydroxy peroxides such as hydrogen peroxide, cumene hydroperoxide, and tert-butyl hydroperoxide; persulfates (potassium, sodium or ammonium salts), tert-butyl peracetate, peresters (tert-butyl perbenzoate), etc. can be listed. As metal ions, Fe 2+ Cr 2+ 、V 2+ 、Co 2+ 、Ti 3+ , Cu + etc. are metal ions that can accept single electron migration. As reducing compounds, sodium bisulfite, sodium bicarbonate, tartaric acid, fructose, glucose, sorbitol, inositol, Rongalite, ascorbic acid can be listed. Among these, preferably, a combination of one or more oxidizing agents selected from hydrogen peroxide, potassium persulfate, sodium persulfate and ammonium persulfate and one or more reducing agents selected from sodium bisulfite, sodium bicarbonate, tartaric acid, Rongalite and ascorbic acid is used, and more preferably, a combination of hydrogen peroxide and one or more reducing agents selected from sodium bisulfite, sodium bicarbonate, tartaric acid, Rongalite and ascorbic acid is used.

[0318] In the emulsion polymerization, an alkali metal compound, a surfactant, a buffer, a polymerization degree regulator, a plasticizer, a film-forming aid, etc. may be appropriately used within a range not impairing the effects of the present invention.

[0319] The alkali metal compound is not particularly limited as long as it contains an alkali metal (sodium, potassium, rubidium, or cesium), and may be an alkali metal ion itself or a compound containing an alkali metal.

[0320] The content of the alkali metal compound (alkali metal conversion) can be appropriately selected according to the type of alkali metal compound used. The content of the alkali metal compound (alkali metal conversion) relative to the total mass of the aqueous emulsion (solid conversion) is preferably 100 to 15000 ppm, more preferably 120 to 12000 ppm, and further preferably 150 to 8000 ppm. When the content of the alkali metal compound is less than 100 ppm, there is a tendency for the emulsion polymerization stability to decrease. On the other hand, when it exceeds 15000 ppm, there is a tendency for the obtained coating to be colored. It should be noted that the content of the alkali metal compound can be measured using an ICP emission spectrometer. In this specification, "ppm" refers to "mass ppm".

[0321] Specific examples of the compound containing an alkali metal include weakly basic alkali metal salts (e.g., alkali metal carbonates, alkali metal acetates, alkali metal hydrogen carbonates, alkali metal phosphates, alkali metal sulfates, alkali metal halide salts, alkali metal nitrates), strongly basic alkali metal compounds (e.g., alkali metal hydroxides, alkali metal alkoxides), etc. These alkali metal compounds may be used alone or in combination of two or more.

[0322] As the weakly basic alkali metal salt, for example, alkali metal carbonates (such as sodium carbonate, potassium carbonate, rubidium carbonate, cesium carbonate), alkali metal bicarbonates (such as sodium bicarbonate, potassium bicarbonate, etc.), alkali metal phosphates (sodium phosphate, potassium phosphate, etc.), alkali metal carboxylates (sodium acetate, potassium acetate, cesium acetate, etc.), alkali metal sulfates (sodium sulfate, potassium sulfate, cesium sulfate, etc.), alkali metal halide salts (cesium chloride, cesium iodide, potassium chloride, sodium chloride, etc.), alkali metal nitrates (sodium nitrate, potassium nitrate, cesium nitrate, etc.). Among these, from the viewpoint of alkalinity in the emulsion, it is preferred to use alkali metal carboxylates, alkali metal carbonates, and alkali metal bicarbonates that act in the form of salts of weak acids and strong bases during dissociation, and more preferably alkali metal carboxylates.

[0323] By using these weakly basic alkali metal salts, the weakly basic alkali metal salts function as a pH buffer in the emulsion polymerization, and thus the emulsion polymerization can be stably performed.

[0324] As a surfactant, any one of a nonionic surfactant, an anionic surfactant and a cationic surfactant can be used. As a nonionic surfactant, it is not particularly limited, and examples thereof include polyoxyethylene alkyl ether, polyoxyethylene alkylphenyl ether, polyoxyethylene fatty acid ester, polyoxyalkylene alkyl ether, polyoxyethylene derivative, sorbitan fatty acid ester, polyoxyethylene sorbitan fatty acid ester, polyoxyethylene sorbitan fatty acid ester, glycerol fatty acid ester, etc. As an anionic surfactant, it is not particularly limited, and examples thereof include alkyl sulfate, alkyl aryl sulfate, alkyl sulfonate, sulfate of hydroxyalkanol, sulfosuccinate, sulfate and phosphate of alkyl or alkyl aryl polyethoxyalkanol, etc. As a cationic surfactant, it is not particularly limited, and examples thereof include alkylamine salt, quaternary ammonium salt, polyoxyethylene alkylamine, etc. From the viewpoint of water resistance, warm water resistance and boiling resistance, the amount of surfactant used is preferably less than 2% by mass relative to the total amount of ethylenically unsaturated monomers (e.g. vinyl acetate).

[0325] Examples of buffering agents include acids such as acetic acid, hydrochloric acid, and sulfuric acid; bases such as ammonia, amines, sodium hydroxide, potassium hydroxide, and calcium hydroxide; or basic carbonates, phosphates, and acetates. Examples of polymerization degree modifiers include thiols and alcohols.

[0326] The aqueous emulsion of the present invention may be added with the conventionally known plasticizer or film-forming aid shown below. Examples of the plasticizer or film-forming aid include dimethyl phthalate, diethyl phthalate, dipentyl phthalate, dibutyl phthalate, acetyl tributyl citrate, diisobutyl adipate, dibutyl sebacate, dimethyl glycol adipate, dimethyl glycol sebacate, diethyl glycol sebacate, dimethyl glycol phthalate, diethylene glycol phthalate, dibutyl glycol phthalate, and dibutyl glycol phthalate. Acid ester, tricresyl phosphate, dioctyl phthalate, TEXANOL, polyethylene glycol monophenyl ether, polypropylene glycol monophenyl ether, benzyl alcohol, butyl carbitol acetate, butyl carbitol, 3-methyl-3-methoxybutanol, ethylene glycol, acetylene glycol butyl cellosolve, ethylene cellosolve, butyl cellosolve, chlorinated biphenyl, propylene glycol-mono-2-ethylhexanoate, diethylene glycol monobutyl ether, dipropylene glycol monobutyl ether, etc. The amount of the plasticizer or film-forming aid added is preferably 1 to 200 parts by mass, more preferably 2 to 50 parts by mass, relative to 100 parts by mass of the polymer containing the ethylenically unsaturated monomer.

[0327] In the aqueous emulsion of the present invention, the following known fillers, fillers or pigments can be added after emulsion polymerization. As fillers, fillers or pigments, calcium carbonate, kaolin clay, steatite clay, talc, titanium oxide, iron oxide, pulp, various resin powders, mica, sericite, bentonite, asbestos, calcium silicate, aluminum silicate, diatomaceous earth, silica, anhydrous silicic acid, hydrous silicic acid, magnesium carbonate, aluminum hydroxide, barium sulfate, calcium sulfate, carbon black, etc. can be listed. As the addition amount when adding fillers, fillers or pigments, 1 to 200 parts by mass can be preferably listed, and 20 to 150 parts by mass can be more preferably listed relative to 100 parts by mass of the polymer (Y1) containing ethylenically unsaturated monomers.

[0328] The aqueous emulsion of the present invention obtained by the above method is mainly used for bonding purposes such as woodworking and paper processing, and can be used for coatings, fiber processing, etc., among which it is suitable for bonding purposes. The aqueous emulsion can be used in its original state. If necessary, various existing well-known emulsions and commonly used additives can be used in combination to prepare an emulsion composition within the scope that does not damage the effect of the present invention. As additives, for example, organic solvents (aromatic compounds such as toluene and xylene; alcohols, ketones, esters, halogen-containing solvents, etc.), cross-linking agents, surfactants, plasticizers, anti-precipitation agents, thickeners, fluidity improvers, preservatives, defoamers, fillers, wetting agents, colorants, binders, water-retaining agents, etc. can be listed. They can be used alone or in combination of two or more. As cross-linking agents, for example, polyisocyanate compounds; hydrazine compounds; polyamide polyamine epichlorohydrin resins (PAE); water-soluble aluminum salts such as aluminum chloride and aluminum nitrate; glyoxal resins such as urea-glyoxal resins, etc. The polyisocyanate compound is a compound having two or more isocyanate groups in the molecule. Examples of the polyisocyanate compound include toluene diisocyanate (TDI), hydrogenated TDI, trimethylolpropane-TDI adduct (e.g., "Desmodur L" of Bayer), triphenylmethane triisocyanate, methylene diphenyl isocyanate (MDI), polymethylene polyphenyl polyisocyanate (PMDI), hydrogenated MDI, polymeric MDI, hexamethylene diisocyanate (HDI), xylylene diisocyanate (XDI), 4,4-dicyclohexylmethane diisocyanate, isophorone diisocyanate (IPDI), etc. As the polyisocyanate compound, a prepolymer having an isocyanate group at the terminal group obtained by polymerizing a polyol in advance with an excess of polyisocyanate can be used. The crosslinking agent can be used alone or in combination of two or more. The content of the crosslinking agent is preferably 1 to 50 parts by mass relative to 100 parts by mass of the polymer (Y1). When the content of the crosslinking agent is 1 part by mass or more, the water resistance and heat resistance of the emulsion composition are more excellent. On the other hand, when the content of the crosslinking agent is 50 parts by mass or less, a good film is easily formed, and the water resistance and heat resistance are more excellent.

[0329] As adherends of the adhesive obtained by the above method, paper, wood, plastic, etc. can be applied. Among these materials, the adhesive is particularly suitable for wood and can be applied to laminated boards, plywood, decorative plywood, fiberboard, etc.

[0330] The aqueous emulsion of the present invention can be used in a wide range of applications, such as inorganic binders, cement admixtures, mortar primers, etc. Furthermore, the aqueous emulsion can be effectively used in the form of a so-called powdered emulsion obtained by powdering the obtained aqueous emulsion by spray drying or the like.

[0331] [Dispersion stabilizer for suspension polymerization]

[0332] The dispersion stabilizer for suspension polymerization of vinyl compounds of the present invention comprises a vinyl alcohol polymer (X) obtained by polymerizing and saponifying a plant-derived vinyl ester monomer (A) and a petroleum-derived vinyl ester monomer (B), wherein the molar ratio of (A) / (B) is 5 / 95 to 100 / 0.

[0333] The PVA (X) of the present invention is suitable for use as a dispersion stabilizer for polymerization of a vinyl compound (hereinafter also referred to as a "vinyl monomer") used as a monomer, and can be suitably used for suspension polymerization of the vinyl monomer. As a suitable embodiment of the present invention, a method for producing a vinyl resin can be listed, which includes: a step of performing suspension polymerization of a vinyl compound in the presence of the aforementioned dispersion stabilizer for suspension polymerization.

[0334] Examples of vinyl monomers include halogenated vinyls such as vinyl chloride; vinyl ester monomers such as vinyl acetate and vinyl propionate; (meth)acrylic acid, their esters and salts; maleic acid, fumaric acid, their esters and anhydrides; styrene, acrylonitrile, vinylidene chloride, vinyl ether, and the like. Among these, suspension polymerization of vinyl chloride alone or together with a monomer copolymerizable with vinyl chloride is suitable. Examples of monomers copolymerizable with vinyl chloride include vinyl ester monomers such as vinyl acetate and vinyl propionate; (meth)acrylic acid esters such as methyl (meth)acrylate and ethyl (meth)acrylate; α-olefins such as ethylene and propylene; unsaturated dicarboxylic acids such as maleic anhydride and itaconic acid; acrylonitrile, styrene, vinylidene chloride, vinyl ether, and the like.

[0335] The medium used in the suspension polymerization is preferably an aqueous medium. Examples of the aqueous medium include water or a medium containing water and an organic solvent. The amount of water in the aqueous medium is preferably 90% by mass or more.

[0336] The amount of the dispersant used in the suspension polymerization is not particularly limited, but is usually 1 part by mass or less, preferably 0.01 to 0.5 parts by mass, based on 100 parts by mass of the vinyl compound.

[0337] Regarding the mass ratio of the aqueous medium to the vinyl compound when the vinyl compound is subjected to suspension polymerization, the aqueous medium / vinyl compound (mass ratio) is usually preferably 0.9 to 1.2.

[0338] In the suspension polymerization of vinyl monomers, oil-soluble or water-soluble polymerization initiators that have been used in the polymerization of vinyl chloride monomers and the like can be used. Examples of oil-soluble polymerization initiators include peroxydicarbonate compounds such as diisopropyl peroxydicarbonate, di(2-ethylhexyl) peroxydicarbonate, and diethoxyethyl peroxydicarbonate; perester compounds such as tert-butyl peroxyneodecanoate, tert-butyl peroxyvalerate, tert-hexyl peroxyvalerate, and α-cumyl peroxyneodecanoate; peroxides such as acetylcyclohexylsulfonyl peroxide, 2-peroxyphenoxyacetic acid 2,4,4-trimethylpentyl ester, 3,5,5-trimethylhexanoyl peroxide, and lauroyl peroxide; and azo compounds such as azobis-2,4-dimethylvaleronitrile and azobis(4-2,4-dimethylvaleronitrile). Examples of water-soluble polymerization initiators include potassium persulfate, ammonium persulfate, hydrogen peroxide, and cumene hydroperoxide. These oil-soluble or water-soluble polymerization initiators may be used alone or in combination of two or more.

[0339] During the suspension polymerization of the vinyl monomer, various other additives may be added to the polymerization reaction system as required. Examples of additives include polymerization degree regulators such as aldehydes, halogenated hydrocarbons, and mercaptans; polymerization inhibitors such as phenol compounds, sulfur compounds, and N-oxide compounds; and pH regulators, crosslinking agents, and the like.

[0340] In the suspension polymerization of vinyl monomers, the polymerization temperature is not particularly limited and can be adjusted to a low temperature of about 20° C. or a high temperature of more than 90° C. In addition, in order to improve the heat removal efficiency of the polymerization reaction system, it is also one of the preferred embodiments to use a polymerization reactor equipped with a reflux condenser.

[0341] Additives such as preservatives, mildew inhibitors, anti-blocking agents, defoamers, etc. commonly used in suspension polymerization can be mixed into the dispersion stabilizer as needed. The content of such additives is usually 1.0 mass % or less. One additive can be used alone or in combination of two or more.

[0342] When the PVA (X) of the present invention is used as a dispersion stabilizer for suspension polymerization, the dispersion stabilizer may be used alone or together with water-soluble cellulose ethers such as methylcellulose, hydroxyethylcellulose, hydroxypropylcellulose, and hydroxypropylmethylcellulose; water-soluble polymers such as polyvinyl alcohol and gelatin; oil-soluble emulsifiers such as sorbitan monolaurate, sorbitan trioleate, glyceryl tristearate, and ethylene oxide propylene oxide block copolymer; water-soluble emulsifiers such as polyoxyethylene sorbitan monolaurate, polyoxyethylene glyceryl oleate, and sodium laurate. These may be used alone or in combination of two or more.

[0343] When the PVA (X) of the present invention is used as a dispersion stabilizer for suspension polymerization, a water-soluble or water-dispersible dispersion stabilization aid can be used in combination. As a dispersion stabilization aid, a vinyl alcohol polymer (Y2) (hereinafter sometimes abbreviated as PVA (Y2)) can be used. As PVA (Y2) used as a dispersion stabilization aid, for example, a partially saponified PVA having a saponification degree of less than 65 mol% can be listed. The saponification degree of the partially saponified PVA is preferably 20 mol% or more and less than 60 mol%, more preferably 25 mol% or more and 58 mol% or less, and further preferably 30 mol% or more and 56 mol% or less. In addition, as the degree of polymerization of other PVA (Y2), it is preferably 50 or more and 750 or less, more preferably 100 or more and 700 or less, further preferably 120 or more and 650 or less, and particularly preferably 150 or more and 600 or less. The method for determining the saponification degree and polymerization degree of PVA (Y2) is the same as that of PVA (X). In a suitable embodiment, PVA (Y2) is a dispersion stabilizing agent in which the degree of saponification is less than 65 mol % and the degree of polymerization is 50 or more and 750 or less. In other suitable embodiments, PVA (Y2) is a dispersion stabilizing agent in which the degree of saponification is 30 mol % or more and less than 60 mol % and the degree of polymerization is 180 or more and 650 or less. The PVA (Y2) used in the dispersion stabilizing agent may be a conventional vinyl alcohol polymer obtained by polymerizing and saponifying a vinyl ester monomer derived from petroleum, or may be a vinyl alcohol polymer obtained by polymerizing and saponifying a vinyl ester monomer (A) derived from a plant and a vinyl ester monomer (B) derived from petroleum. In addition, the dispersion stabilizing agent may be endowed with self-emulsifying properties by introducing ionic groups such as carboxylic acids or sulfonic acids.

[0344] The mass ratio of the amount of dispersion stabilizer and dispersion stabilization aid added when the dispersion stabilization aid is used in combination (dispersion stabilizer / dispersion stabilization aid) varies depending on the type of dispersion stabilizer used, and therefore cannot be generalized, but is preferably in the range of 95 / 5 to 20 / 80, and more preferably 90 / 10 to 30 / 70. The dispersion stabilizer and the dispersion stabilization aid may be added together at the initial stage of polymerization, or may be added in batches during the polymerization process.

[0345] [Dispersion stabilizing agent for suspension polymerization]

[0346] The vinyl alcohol polymer (PVA) used in the present invention comprises a vinyl alcohol polymer (X) obtained by polymerizing and saponifying a plant-derived vinyl ester monomer (A) and a petroleum-derived vinyl ester monomer (B), wherein the molar ratio of (A) / (B) is 5 / 95 to 100 / 0.

[0347] One suitable use of the PVA (X) of the present invention is as a dispersion stabilizing agent for polymerization of vinyl compounds used as monomers, and can be suitably used for suspension polymerization of vinyl monomers. As vinyl monomers, the same monomers as those described for the dispersion stabilizer for suspension polymerization can be cited.

[0348] The medium used in the suspension polymerization is preferably an aqueous medium. Examples of the aqueous medium include water or a medium containing water and an organic solvent. The amount of water in the aqueous medium is preferably 90% by mass or more.

[0349] In the suspension polymerization of the vinyl monomer, an oil-soluble or water-soluble polymerization initiator conventionally used in the polymerization of vinyl chloride monomers etc. can be used. Examples of the oil-soluble or water-soluble polymerization initiator include the same ones as described for the dispersion stabilizer for suspension polymerization.

[0350] During the suspension polymerization of the vinyl monomer, various other additives may be added to the polymerization reaction system as required. Examples of additives include polymerization degree regulators such as aldehydes, halogenated hydrocarbons, and mercaptans; polymerization inhibitors such as phenol compounds, sulfur compounds, and N-oxide compounds; and pH regulators, crosslinking agents, and the like.

[0351] In the suspension polymerization of vinyl monomers, the polymerization temperature is not particularly limited and can be adjusted to a low temperature of about 20° C. or a high temperature of more than 90° C. In addition, in order to improve the heat removal efficiency of the polymerization reaction system, it is also one of the preferred embodiments to use a polymerization reactor equipped with a reflux condenser.

[0352] Additives such as preservatives, mildew inhibitors, anti-blocking agents, defoamers, etc. commonly used in suspension polymerization can be mixed into the dispersion stabilizing agent as needed. The content of such additives is usually 1.0 mass % or less. One additive can be used alone or in combination of two or more.

[0353] The dispersion stabilization aid of the present invention can be used in combination with a dispersion stabilizer for suspension polymerization. As another suitable embodiment of the present invention, there can be cited a method for producing a vinyl resin, which comprises: in the presence of the aforementioned dispersion stabilization aid and a dispersion stabilizer for suspension polymerization, a step of suspension polymerization of a vinyl compound, wherein the dispersion stabilizer for suspension polymerization contains a vinyl alcohol polymer (Y3) having a saponification degree of 65 mol% or more and a viscosity average polymerization degree of 600 or more (hereinafter sometimes abbreviated as PVA (Y3)).

[0354] When the PVA (X) of the present invention is used as a dispersion stabilizing agent for suspension polymerization, a dispersion stabilizer comprising PVA (Y3) may be used in combination. PVA (Y3) may be a vinyl alcohol polymer obtained by polymerizing and saponifying a vinyl ester monomer derived from petroleum, or may be a vinyl alcohol polymer (Y3-1) obtained by polymerizing and saponifying a vinyl ester monomer (A) derived from a plant and a vinyl ester monomer (B) derived from petroleum.

[0355] The viscosity average degree of polymerization of PVA (Y3) is preferably 150 or more and 5,000 or less, more preferably 300 or more and 4,000 or less, and further preferably 600 or more and 3500 or less. The saponification degree of PVA (Y3) is preferably 60 mol% or more and 99.5 mol%, more preferably 65 mol% or more and 99.2 mol% or less, and further preferably 68 mol% or more and 99.0 mol% or less. The method for determining the saponification degree and polymerization degree of PVA (Y3) is the same as that of PVA (X). PVA (Y3) can be manufactured using a conventionally known method. The method for manufacturing the vinyl alcohol polymer (Y3-1) is the same as that of PVA (X). The polymerization conditions and saponification conditions can be appropriately set to the aforementioned desired range. In a suitable embodiment, the saponification degree of PVA (Y3) is 65 mol% or more and the viscosity average degree of polymerization is 600 or more. In another preferred embodiment, the viscosity average degree of polymerization is 500 to 5000, and the degree of saponification is 65 mol % to 99 mol %.

[0356] The mass ratio of the amount of dispersion stabilizer and dispersion stabilization aid added when a dispersion stabilizer is used in combination (dispersion stabilizer / dispersion stabilization aid) varies depending on the type of dispersion stabilizer used, and therefore cannot be generalized, but is preferably in the range of 95 / 5 to 20 / 80, more preferably 90 / 10 to 30 / 70. The dispersion stabilizer and the dispersion stabilization aid may be added together at the initial stage of polymerization, or may be added in batches during the polymerization process.

[0357] The aforementioned dispersion stabilizing aid for suspension polymerization can be used in combination with water-soluble cellulose ethers such as methylcellulose, hydroxyethylcellulose, hydroxypropylcellulose, and hydroxypropylmethylcellulose, which are commonly used when suspending and polymerizing vinyl compounds in aqueous media; water-soluble polymers such as gelatin; oil-soluble emulsifiers such as sorbitan monolaurate, sorbitan trioleate, glyceryl tristearate, and ethylene oxide propylene oxide block copolymers; water-soluble emulsifiers such as polyoxyethylene sorbitan monolaurate, polyoxyethylene glyceryl oleate, and sodium laurate, etc. There is no particular limitation on the amount of addition, but it is preferably 0.01 parts by mass or more and 1.0 parts by mass or less relative to 100 parts by mass of the vinyl compound.

[0358] During the suspension polymerization of the vinyl compound, the method of adding the above-mentioned dispersion stabilization aid for suspension polymerization into the polymerization tank is not particularly limited. An aqueous solution of the dispersion stabilization aid for suspension polymerization can be prepared and fed. In addition, a mixed solution of water and methanol or ethanol of the dispersion stabilization aid for suspension polymerization can be prepared and fed. In addition, the above-mentioned dispersion stabilization aid for suspension polymerization can be mixed with an aqueous solution containing the dispersion stabilization aid for suspension polymerization and fed. In addition, the aqueous solution of the dispersion stabilization aid for suspension polymerization and the aqueous solution of the dispersion stabilization aid for suspension polymerization can be fed separately.

[0359] During the suspension polymerization of the vinyl compound, the amount of the dispersion stabilization aid for suspension polymerization added to the polymerization tank is not particularly limited. It is preferred that the aqueous solution of the dispersion stabilization aid for suspension polymerization be added in such a manner that the amount of PVA (X) relative to the vinyl compound (e.g., vinyl chloride monomer) becomes 30 ppm or more and 1000 ppm or less, more preferably 50 ppm or more and 800 ppm or less, and even more preferably 100 ppm or more and 500 ppm or less.

[0360] By subjecting a vinyl compound to suspension polymerization in the presence of the above-mentioned dispersion stabilization auxiliary agent for suspension polymerization by the above-mentioned method, it is possible to obtain vinyl polymer particles having high plasticizer absorption, no foreign matter such as fish eyes, little formation of coarse particles, and easy removal of residual monomer components. The obtained vinyl polymer particles can be appropriately blended with a plasticizer and the like and used for various molded product applications.

[0361] Example

[0362] The present invention will be described in more detail below with reference to Examples, but the present invention is not limited to these Examples. In the examples, "parts" and "%" are by mass unless otherwise specified.

[0363] (Content ratio of ethylene units in ethylene-modified PVA)

[0364] The content of ethylene units in the ethylene-modified PVA is determined by the precursor or re-saponification product of the ethylene-modified PVA, i.e., the ethylene-modified vinyl ester polymer. 1 Specifically, the ethylene-modified vinyl ester polymers of the samples of Synthesis Examples 7-3 and 7-5 were reprecipitated and purified three or more times using a mixed solution of n-hexane and acetone, and then dried under reduced pressure at 80°C for 3 days to prepare ethylene-modified vinyl ester polymers for analysis. The ethylene-modified vinyl ester polymers for analysis were dissolved in DMSO-d6 and measured at 80°C. 1H-NMR (500 MHz): The ethylene unit content was calculated by the following formula using the peak derived from the main chain methine protons of vinyl acetate (integrated value P: 4.7 to 5.2 ppm) and the peak derived from the main chain methylene protons of ethylene and vinyl acetate (integrated value Q: 1.0 to 1.6 ppm).

[0365] Ethylene unit content (mol%) = 100 × ((Q-2P) / 4) / P

[0366] (Viscosity average degree of polymerization of PVA)

[0367] The viscosity average polymerization degree of PVA is measured in accordance with JIS K6726: 1994. Specifically, when the degree of saponification is less than 99.5 mol%, the viscosity average polymerization degree is determined by the following formula using the intrinsic viscosity [η] (dL / g) measured in water at 30°C for PVA or ethylene-modified PVA saponified to a degree of saponification of 99.5 mol% or more.

[0368] Viscosity average degree of polymerization = ([η] × 1000 / 8.29) (1 / 0.62)

[0369] (Saponification degree of PVA)

[0370] The saponification degree of PVA is measured in accordance with JIS K 6726:1994.

[0371] (Synthesis Example 1-1)

[0372] The silica spherical carrier is impregnated with an aqueous solution containing an aqueous solution of sodium tetrachloropalladate and an aqueous solution of tetrachloroauric acid tetrahydrate and equivalent to the water absorption of the carrier, and is immersed in an aqueous solution containing sodium metasilicate nonahydrate and allowed to stand. Next, an aqueous solution of hydrazine hydrate is added, and after standing at room temperature, it is washed with water until the chloride ions in the water disappear, and then dried. The palladium / gold / carrier composition is immersed in an acetic acid aqueous solution and allowed to stand. Next, it is washed with water and dried. Thereafter, it is impregnated in an aqueous solution of potassium acetate equivalent to the water absorption of the carrier, and dried, thereby obtaining a vinyl acetate synthesis catalyst.

[0373] The catalyst obtained above was diluted with glass beads and filled into a SUS reaction tube, and a mixed gas of ethylene, oxygen, water, acetic acid and nitrogen was circulated to react. Bioethylene derived from sugar cane (manufactured by Braskem SA) was used as ethylene. In addition, acetic acid was gasified and then introduced into the reaction system by steam. The yield and selectivity of vinyl acetate were obtained by analyzing the reaction outlet gas. The obtained vinyl acetate was analyzed by the above method, and the 14 The result of C / C is 5.0×10 -13 .

[0374] (Synthesis Example 1-2)

[0375] 50 parts of plant-derived vinyl acetate and 50 parts of ordinary petroleum-derived vinyl acetate obtained in Synthesis Example 1-1 above were uniformly mixed and used as raw materials to synthesize PVA by the following method.

[0376] 127.5 kg of the above vinyl acetate and 22.5 kg of methanol were charged into a 250 L reaction tank equipped with a stirrer, a nitrogen inlet, an ethylene inlet, an initiator addition port, and a retarder solution addition port. After heating to 60 °C, nitrogen replacement was carried out by nitrogen bubbling for 30 minutes. Then, ethylene was introduced in such a way that the pressure in the reaction tank became 3.4 Kg / cm 2 2,2'-azobis(4-methoxy-2,4-dimethylvaleronitrile) (AMV) as an initiator was dissolved in methanol to prepare a reaction initiation solution with a concentration of 2.8 g / L, and nitrogen replacement was carried out by bubbling nitrogen through this reaction initiation solution. 45 mL of this initiator solution was injected into the reaction tank adjusted to 60 °C to start polymerization. During polymerization, ethylene was introduced to maintain the pressure in the reaction tank at 3.4 kg / cm 2 , and the polymerization temperature was maintained at 60 °C. The initiator solution was continuously added to the reaction tank at 143 mL / hr to carry out polymerization. When the polymerization rate reached 50% after 5 hours, the reaction tank was cooled to stop polymerization. Furthermore, after opening the reaction tank to remove ethylene, nitrogen was bubbled to completely remove ethylene. Then, unreacted vinyl acetate monomer was removed under reduced pressure to prepare a methanol solution of polyvinyl acetate. Methanol was added to this polyvinyl acetate solution to adjust the concentration of polyvinyl acetate to 25% by mass. Furthermore, 23.3 g (0.1 in molar ratio relative to the vinyl acetate units in polyvinyl acetate) of an alkali solution (10% by mass methanol solution of NaOH) was added to 400 g of this methanol solution of polyvinyl acetate (100 g of polyvinyl acetate in the solution) for saponification. About 1 minute after adding the alkali, the gelled substance was pulverized with a pulverizer, and after standing at 40 °C for 1 hour for saponification, 1000 g of methyl acetate was added and left at room temperature for 30 minutes. 1000 g of methanol was added to the white solid (PVA) obtained by filtration, and after standing and washing at room temperature for 3 hours, centrifugal dewatering was carried out, and the PVA thus obtained was placed in a dryer at 100 °C for 3 hours to obtain PVA (PVA1-1).

[0377] (Characteristic Analysis of PVA)

[0378] For PVA (PVA1-1), the degree of saponification, the average degree of polymerization, and the proportion of ethylene units were analyzed according to the following method.

[0379] (Degree of Saponification)

[0380] The saponification degree of PVA (PVA1-1) was measured in accordance with JIS K 6726:1994 and was 99.5 mol %.

[0381] (Average degree of polymerization)

[0382] The methanol solution of polyvinyl acetate obtained by removing the unreacted vinyl acetate monomer after polymerization in Synthesis Example 1-2 was saponified at an alkali molar ratio of 0.5, and then pulverized. The obtained substance was placed at 60° C. for 5 hours for saponification. Thereafter, methanol Soxhlet extraction was performed for 3 days, and then vacuum drying was performed at 80° C. for 3 days to obtain purified PVA. The average degree of polymerization of the purified PVA was measured in accordance with JIS K6726:1994 and was 2,450.

[0383] (Ratio of ethylene units)

[0384] The methanol solution of polyvinyl acetate obtained by removing the unreacted vinyl acetate monomer after polymerization in Synthesis Example 1-2 was subjected to reprecipitation purification by precipitation in n-hexane and dissolution in acetone three times, and then dried under reduced pressure at 80° C. for 3 days to obtain purified polyvinyl acetate. The purified polyvinyl acetate was dissolved in DMSO-d6, and the content of ethylene units was measured at 80° C. using a 500 MHz proton NMR (JEOL GX-500), which was 3.0 mol %.

[0385] (Synthesis Example 1-3)

[0386] 30 parts of the plant-derived vinyl acetate obtained in the above-mentioned Synthesis Example 1-1 and 70 parts of the common petroleum-derived vinyl acetate were uniformly mixed and used as raw materials, and PVA (PVA1-2) was synthesized by the method based on Synthesis Example 1-2 except that ethylene was not introduced. PVA1-2 had a saponification degree of 99.5 mol%, an average polymerization degree of 2,640, and an ethylene unit of 0 mol%.

[0387] (Synthesis Example 1-4)

[0388] Using vinyl acetate commonly derived from petroleum as 100% of the raw material, PVA (PVA1-3) was synthesized by the same method as in Synthesis Example 1-2. PVA1-3 had a saponification degree of 99.6 mol%, an average polymerization degree of 2,480, and an ethylene unit of 3.0 mol%.

[0389] (Synthesis Example 1-5)

[0390] Using vinyl acetate commonly derived from petroleum as 100% of the raw material, PVA (PVA1-4) was synthesized by the same method as in Synthesis Example 1-3. PVA1-4 had a saponification degree of 99.6 mol%, an average polymerization degree of 2,580, and an ethylene unit of 0 mol%.

[0391] [Example 1-1]

[0392] <Preparation of cement slurry>

[0393] PVA (PVA1-1) was placed on a sieve with a nominal mesh size of 250 μm (60 mesh), and 4 g of the PVA powder that passed through the sieve was put into a juice blender together with 320 g of ion exchange water, 800 g of H-grade cement for mines, 4 g of sodium salt of naphthalenesulfonic acid formaldehyde condensate ("Daxad-19" from Dipersity Technologies) and 0.16 g of sodium salt of lignin sulfonate ("Keling32L" from Lignotech USA) and stirred and mixed to prepare cement slurry (S-1). It should be noted that the amount of PVA powder added was set to 0.5% based on the mass basis (BWOC) of cement. As described above, the PVA powder was screened to have a particle size of less than 250 μm based on particle size distribution (volume basis).

[0394] [Example 1-2]

[0395] A cement slurry (S-2) was prepared in the same manner as in Example 1-1 except that PVA (PVA1-2) was used.

[0396] [Reference Example 1-1]

[0397] A cement slurry (s-1) was prepared in the same manner as in Example 1-1 except that PVA (PVA1-3) was used.

[0398] [Reference Example 1-2]

[0399] A cement slurry (s-2) was prepared in the same manner as in Example 1-2 except that PVA (PVA1-4) was used.

[0400] [evaluate]

[0401] The viscosity and dehydration amount of the cement slurries (S-1), (S-2) and (s-1), (s-2) of Examples 1-1, 1-2 and Reference Examples 1-1, 1-2 were evaluated by the following method. The evaluation results are shown in Table 1. In addition, the solubility of PVA in water used in the preparation of these cement slurries is shown in Table 1.

[0402] <Solubility in water>

[0403] 4 g of PVA powder was added to a 300 mL beaker pre-filled with 100 g of 60°C water, and stirred at 280 rpm for 3 hours at 60°C using a magnetic stirrer with a 3 cm long rod without evaporating the water. Next, a metal mesh with a nominal mesh size of 75 μm (200 mesh) was used to separate the undissolved powder. The undissolved PVA powder was dried for 3 hours in a heating dryer at 105°C, and its mass was measured. The solubility of the PVA powder was calculated based on the mass of the undissolved PVA powder and the mass of the PVA powder put into the beaker (4 g).

[0404] <stickiness>

[0405] Viscosity is evaluated in the form of plastic viscosity (PV) and yield strength (YV). Plastic viscosity (PV) is the flow resistance value caused by mechanical friction of the solid components contained in the cement slurry. Yield strength (YV) is the shear force necessary for the continuous flow of the fluid when it is in a flowing state, and is the flow resistance caused by the traction between the solid particles contained in the cement slurry.

[0406] The plastic viscosity (PV) and the yield strength (YV) were measured by adjusting the temperature of the cement slurry to 25°C or 90°C according to the method described in "Appendix H" of "API10" (American Institute Specification 10). The plastic viscosity (PV) and the yield strength (YV) were calculated using the following formula.

[0407] Plastic viscosity (PV) = (300 rpm reading - 100 rpm reading) × 1.5

[0408] Yield force (YV) = (300 rpm reading - plastic viscosity)

[0409] <Dehydration amount>

[0410] The dewatering amount was measured by the method described in "Appendix H" of "API 10" (American Institute Specification 10) as the dewatering amount of cement slurry adjusted to 90°C under a pressure difference of 1000 psi for 30 minutes.

[0411] [Table 1]

[0412]

[0413] It is clear from the results in Table 1 that the cement slurries (S-1) and (S-2) of Examples 1-1 and 1-2 have excellent viscosity, and the dehydration amounts at 150°C are 25 mL and 32 mL, respectively, and dehydration at high temperatures is suppressed. Moreover, their values ​​are not inferior to those of PVA synthesized only from vinyl acetate derived from petroleum, i.e., the cement slurries (s-1) and (s-2) of Reference Examples 1-1 and 1-2, and have equivalent performance as cement slurries. In addition, it was visually confirmed that the cement slurries (S-1) and (S-2) of Examples 1-1 and 1-2 did not separate. This cement slurry can help save petroleum resources and inhibit global warming.

[0414] <Drilling Mud>

[0415] (Synthesis Example 1-6) Preparation of PVA (PVA1-5)

[0416] 50 parts of the plant-derived vinyl acetate obtained in the above Synthesis Example 1-1 and 50 parts of common petroleum-derived vinyl acetate were uniformly mixed and used as raw materials, and PVA was synthesized by the following method.

[0417] 127.5 kg of vinyl acetate and 22.5 kg of methanol were added to a 250 L reaction tank equipped with a stirrer, a nitrogen inlet, an ethylene inlet, an initiator addition port, and a delay solution addition port. After the temperature was raised to 60° C., nitrogen was bubbling for 30 minutes to replace the atmosphere with nitrogen. Then, the pressure in the reaction tank was set to 4.9 kg / cm 2 Ethylene was introduced by the method of ethylene. 2,2'-azobis(4-methoxy-2,4-dimethylvaleronitrile) (AMV) as an initiator was dissolved in methanol to prepare a reaction initiation solution with a concentration of 2.8 g / L, and nitrogen was replaced by bubbling the reaction initiation solution with nitrogen. 45 mL of the initiator solution was injected into a reaction tank adjusted to 60°C to start polymerization. During the polymerization, ethylene was introduced to maintain the pressure of the reaction tank at 4.9 Kg / cm 2, and the polymerization temperature was maintained at 60°C, and the initiator solution was continuously added to the reaction tank at 143 mL / hr to conduct the polymerization. When the polymerization rate reached 40% after 4 hours, the reaction tank was cooled to stop the polymerization. Further, the reaction tank was opened to remove ethylene, and then nitrogen was introduced to completely remove ethylene. Next, the unreacted vinyl acetate monomer was removed under reduced pressure to prepare a methanol solution of polyvinyl acetate. Methanol was added to this polyvinyl acetate solution to adjust the concentration of polyvinyl acetate to 25% by mass. Further, 23.3 g (molar ratio of 0.1 based on the vinyl acetate units in polyvinyl acetate) of an alkali solution (10% by mass methanol solution of NaOH) was added to 400 g of this methanol solution of polyvinyl acetate (100 g of polyvinyl acetate in the solution) for saponification. Approximately 1 minute after adding the alkali, the gelled substance was pulverized with a pulverizer, and after standing at 40°C for 1 hour for saponification, 1000 g of methyl acetate was added and left standing at room temperature for 30 minutes. 1000 g of methanol was added to the white solid (PVA) obtained by filtration, and after standing and washing at room temperature for 3 hours, centrifugal dewatering was performed, and the PVA thus obtained was placed in a dryer at 100°C for 3 hours to obtain PVA (PVA1-5).

[0418] <Characteristics Analysis of PVA>

[0419] For PVA (PVA1-5), the degree of saponification, average degree of polymerization, and proportion of ethylene units were analyzed according to the following method.

[0420] (Degree of Saponification)

[0421] The degree of saponification of PVA (PVA1-5) was 99.9 mol% as determined according to JIS K6726:1994.

[0422] (Average Degree of Polymerization)

[0423] The methanol solution of polyvinyl acetate obtained by removing the unreacted vinyl acetate monomer after polymerization in Synthesis Examples 1-6 was saponified at an alkali molar ratio of 0.5, pulverized, and the resulting substance was left standing at 60°C for 5 hours for saponification. Thereafter, methanol Soxhlet extraction was carried out for 3 days, and then vacuum drying was carried out at 80°C for 3 days to obtain purified PVA. The average degree of polymerization of this purified PVA was 1,720 as determined according to JIS K6726:1994.

[0424] (Content of Ethylene Units)

[0425] The methanol solution of polyvinyl acetate obtained by removing the unreacted vinyl acetate monomer after polymerization in Synthesis Example 1-6 was subjected to reprecipitation purification by precipitation in n-hexane and dissolution in acetone three times, and then dried under reduced pressure at 80° C. for 3 days to obtain purified polyvinyl acetate. The purified polyvinyl acetate was dissolved in DMSO-d6 and 500 MHz 1 The ratio of ethylene units was measured by H-NMR (JEOL GX-500) at 80°C and found to be 5.0 mol%.

[0426] (Synthesis Example 1-7) Preparation of PVA (PVA1-6)

[0427] 30 parts of the plant-derived vinyl acetate obtained in the above-mentioned Synthesis Example 1-1 and 70 parts of the common petroleum-derived vinyl acetate were uniformly mixed and used as raw materials, and PVA (PVA1-6) was synthesized by the method based on Synthesis Example 1-6 except that ethylene was not introduced. PVA1-6 had a saponification degree of 99.9 mol%, an average polymerization degree of 2,520, and an ethylene unit of 0 mol%.

[0428] (Synthesis Example 1-8)

[0429] Using vinyl acetate commonly derived from petroleum as 100% of the raw material, PVA (PVA1-7) was synthesized by the same method as in Synthesis Example 1-6. PVA1-7 had a saponification degree of 99.9 mol%, an average polymerization degree of 1,740, and an ethylene unit of 5.0 mol%.

[0430] (Synthesis Example 1-9)

[0431] Using vinyl acetate commonly derived from petroleum as 100% of the raw material, PVA (PVA1-8) was synthesized by the same method as in Synthesis Example 1-7. PVA1-8 had a saponification degree of 99.9 mol%, an average polymerization degree of 2,480, and an ethylene unit of 0 mol%.

[0432] [Examples 1-3]

[0433] <Preparation of drilling mud>

[0434] 300 g of ion exchange water was placed in the cup of Hamilton-Beach (Hamichi) blender, 6 g of bentonite (TELNITE "Telgel E") was added and stirred thoroughly, and then left for 24 hours to allow the bentonite to swell fully. On the other hand, PVA (PVA1-5) was placed on a sieve with a nominal mesh of 1.00 mm (16 mesh), 1.5 g of the powder of PVA (PVA1-5) that passed through the sieve was taken, and the powder was added to the bentonite dispersion to obtain drilling mud (D-1). As described above, the powder of PVA has a particle size of less than 1.00 mm in terms of particle size distribution (volume basis) by sieving.

[0435] [Examples 1-4]

[0436] A drilling mud (D-2) was prepared in the same manner as in Example 1-3 except that the powder of PVA (PVA1-6) was used.

[0437] [Reference Example 1-3]

[0438] A drilling mud (d-1) was prepared in the same manner as in Example 1-3 except that the powder of PVA (PVA1-7) was used.

[0439] [Reference Example 1-4]

[0440] A drilling mud (d-2) was prepared in the same manner as in Example 1-3 except that the powder of PVA (PVA1-8) was used.

[0441] [evaluate]

[0442] The viscosity and water removal amount of the drilling muds (D-1), (D-2) and (d-1), (d-2) were evaluated by the following method. In addition, the solubility in water of PVA (PVA1-5) to (PVA1-8) used in the preparation of these drilling muds was evaluated by the following method. The evaluation results are shown in Table 2.

[0443] <Solubility in water>

[0444] 4 g of PVA powder was added to a 300 mL beaker pre-filled with 100 g of 60°C water, and stirred at 280 rpm for 3 hours at 60°C using a magnetic stirrer with a 3 cm long rod without evaporating the water. Next, a metal mesh with a nominal mesh size of 75 μm (200 mesh) was used to separate the undissolved powder. The undissolved PVA powder was dried for 3 hours in a heating dryer at 105°C, and its mass was measured. The solubility of the PVA powder was calculated based on the mass of the undissolved PVA powder and the mass of the PVA powder put into the beaker (4 g).

[0445] <Viscosity>

[0446] The viscosity of the drilling mud was measured using a B-type viscometer at 25° C. and 30 rpm, and the value after 10 seconds was adopted.

[0447] <Dehydration amount>

[0448] The dewatering amount of drilling mud was measured using "HPHT Filter Press Series 387" from Fann Instrument Co. Drilling mud was placed in a cell adjusted to 150°C and allowed to stand for 3 hours. The cell was then pressurized from the top and bottom to a pressure difference of 500 psi.

[0449] [Table 2]

[0450]

[0451] From the results in Table 2, it is clear that the drilling muds (D-1) and (D-2) of Examples 1-3 and 1-4 have low viscosities and a dehydration amount of 25 mL or less at 150°C, and dehydration at high temperatures is very little suppressed. Moreover, these values ​​are not inferior to those of PVA synthesized only from vinyl acetate derived from petroleum, that is, the drilling muds (d-1) and (d-2) of Reference Examples 1-3 and 1-4, and have equivalent performance as drilling muds. Such drilling muds can contribute to saving petroleum resources and suppressing global warming.

[0452] (Synthesis example 2-2)

[0453] 50 parts of the vinyl acetate derived from plants obtained in the above-mentioned synthesis example 1-1 and 50 parts of the vinyl acetate derived from petroleum are uniformly mixed and used as raw materials. Methyl acrylate is further used to copolymerize 5 mol% of methyl acrylate to synthesize polyvinyl acetate according to a conventional method. It is made into a methanol solution, saponified using an alkali catalyst, and dried to obtain PVA. The average polymerization degree of the PVA is 1,450, and the saponification degree is 99.5 mol%. Polyethylene glycol 1.5 mass % is added to the obtained PVA and mixed. Then, a twin-screw extruder is used to extrude and form into a sheet with a molding pressure of 1259psi. It is put into a granulator and granulated into 6 / 8 mesh (ASTM E11 standard) to obtain PVA resin pellets (PVA2-1). It should be noted that “granulated into 6 / 8 mesh” means granulated into a particle size that passes through 6 mesh but does not pass through 8 mesh, and the particle size of particles granulated into 6 / 8 mesh is 2380 μm or more and 3350 μm or less.

[0454] (Synthesis example 2-3)

[0455] 30 parts of the plant-derived vinyl acetate obtained in the above-mentioned Synthesis Example 1-1 and 70 parts of the usual petroleum-derived vinyl acetate were uniformly mixed and used as raw materials. Except that methyl acrylate was not copolymerized, PVA was obtained by the same method as Synthesis Example 2-2. The average polymerization degree of the PVA was 1,620 and the saponification degree was 99.5 mol%. 1.5 mass % of polyethylene glycol was added to the obtained PVA and kneaded. Then, a twin-screw extruder was used to extrude the sheet at a molding pressure of 1250 psi, and the sheet was put into a granulator and granulated into 6 / 8 mesh to obtain PVA resin pellets (PVA2-2).

[0456] (Synthesis example 2-4)

[0457] Using vinyl acetate commonly derived from petroleum as 100% of the raw material, PVA resin pellets (PVA2-3) were synthesized by the same method as in Synthesis Example 2-2. The PVA had a saponification degree of 99.5 mol%, an average polymerization degree of 1,480, and a methyl acrylate content of 5 mol%.

[0458] (Synthesis example 2-5)

[0459] Using vinyl acetate commonly derived from petroleum as 100% of the raw material, PVA resin pellets (PVA2-4) were synthesized by the same method as in Synthesis Example 2-3. The saponification degree of this PVA was 99.6 mol% and the average degree of polymerization was 1,580.

[0460] [Examples 2-1 and 2-2, Reference Examples 2-1 and 2-2]

[0461] <Filling agent for underground treatment>

[0462] The swelling degree (%) and solubility (%) in water of the obtained PVA2-1 to PVA2-4 were measured by the following method to evaluate the filling effect.

[0463] <Swelling degree based on water>

[0464] 0.5 g of PVA resin pellets were placed in a test tube with an inner diameter of 18 mm, and the height (height A) occupied by the PVA resin pellets in the test tube was measured. Next, 7 mL of distilled water was added to the test tube, and the PVA resin pellets were dispersed by shaking. Thereafter, the test tube was immersed in a water bath set at 40°C. After the water temperature in the test tube reached 40°C, it was allowed to stand for 30 minutes, and the height (height B) occupied by the PVA resin pellets in the test tube was measured. The swelling degree (%) based on water was calculated from the values ​​of the height A and height B obtained according to the following formula.

[0465] Swelling degree based on water (%) = (height B / height A) × 100

[0466] <Solubility in water>

[0467] 100 g of distilled water and 6 g of PVA resin pellets were added to a 200 mL glass container with a lid, and the mixture was allowed to stand in a thermostatic chamber at 65°C for 5 hours. Afterwards, the contents of the glass container were passed through a 120-mesh nylon sieve (a sieve with a mesh size of 125 microns), and the PVA resin pellets remaining on the sieve were dried at 140°C for 3 hours, and the mass after drying (mass A) was measured. On the other hand, for the same measurement object, the PVA resin pellets taken separately from the aforementioned PVA resin pellets for the purpose of measuring the solid content were dried at 105°C for 3 hours, and the mass before drying (mass B) and the mass after drying (mass C) were measured to calculate the solid content. Using the solid content and mass A, the solubility (%) of the PVA resin pellets in water was calculated according to the following formula.

[0468] Solid content (%) = (mass C / mass B) × 100

[0469] Solubility in water (%) = {6-(mass A×100 / solid content)} / 6×100

[0470] <Filling effect confirmation test>

[0471] A 120-mesh stainless steel sieve was placed in a stainless steel column with an inner diameter of 10 mm, and 5 g of PVA resin pellets were added to the upstream side. Next, warm water adjusted to 50° C. was added to the column, and a pressure of 100 psi was applied. The column was visually observed, and the filling effect was evaluated by recording "0" if the outflow of warm water stopped within 15 seconds and "×" if it did not stop within 15 seconds.

[0472] [Table 3]

[0473]

[0474] The solubility and swelling values ​​of the PVA resin pellets of Examples 2-1 and 2-2 are not inferior to those of Reference Examples 2-1 and 2-2, respectively, and it can be confirmed that they have the same degree of (hot) water solubility and swelling. In addition, on the basis of fully exerting the filling effect, it can help save petroleum resources and inhibit global warming. The underground treatment filler containing this PVA temporarily seals the cracks in the ground, and slowly dissolves in water. It is removed when or after the recovery of underground resources such as oil and natural gas, so it will not stay in the ground for a long time, which can reduce the burden on the environment.

[0475] (Synthesis example 2-6)

[0476] 100 parts of the plant-derived vinyl acetate obtained in the above-mentioned Synthesis Example 1-1 was used as a raw material without adding any conventional petroleum-derived vinyl acetate, and PVA was obtained by the same method as Synthesis Example 2-3. The average polymerization degree of the PVA was 1,580 and the saponification degree was 99.6 mol%. 1.5 mass % of polyethylene glycol was added to the obtained PVA and kneaded, and then, after being extruded into a sheet shape using a twin-screw extruder at a molding pressure of 1250 psi, it was put into a granulator and granulated into 6 / 8 mesh to obtain PVA resin pellets (PVA2-5).

[0477] [Comparative Example 2-1]

[0478] The appearance of the obtained PVA2-5 was observed to have cracks, whereas the appearance of PVA2-3 obtained by the same method was smooth. The reason for this is not clear, but it was confirmed that the cracks of PVA can be improved by setting the plant-derived vinyl acetate in the raw material to 10 mol% or more.

[0479] In the present invention, by using a plant-derived vinyl ester monomer (A) as a monomer, a vinyl alcohol polymer having equivalent properties to a vinyl alcohol polymer derived only from petroleum is obtained. It can be confirmed that the occurrence of manufacturing problems generated when manufacturing PVA can be suppressed. Furthermore, when using PVA, petroleum resources can be saved and carbon dioxide emissions in the manufacturing process can be suppressed.

[0480] (Synthesis example 3-2)

[0481] 50 parts of the plant-derived vinyl acetate obtained in the above-mentioned Synthesis Example 1-1 and 50 parts of the usual petroleum-derived vinyl acetate were uniformly mixed and used as raw materials, and the polymerization conditions such as polymerization temperature and polymerization time were adjusted to the desired range, and polyvinyl acetate was synthesized according to the conventional method. It was made into a methanol solution, and the saponification conditions such as the amount of alkali catalyst and saponification time were adjusted to the desired range. The saponification reaction was carried out according to the conventional method and using an alkali catalyst, and dried to obtain PVA (PVA3-1). The average polymerization degree of this PVA was 1,750, and the saponification degree was 88.5 mol%.

[0482] (Synthesis example 3-3)

[0483] PVA (PVA3-2) was obtained by the same method as Synthesis Example 3-2 except that 30 parts of plant-derived vinyl acetate obtained in Synthesis Example 1-1 and 70 parts of common petroleum-derived vinyl acetate were uniformly mixed and used as raw materials, and common petroleum-derived ethylene was copolymerized. The average polymerization degree of this PVA was 1,720, the saponification degree was 97.5 mol%, and the ethylene content was 4.2 mol%.

[0484] (Synthesis Example 3-4)

[0485] A PVA resin (PVA3-3) was synthesized by the same method as in Synthesis Example 3-2 using vinyl acetate commonly derived from petroleum as 100% of the raw material. The PVA had a saponification degree of 88.7 mol% and an average polymerization degree of 1,780.

[0486] (Synthesis Example 3-5)

[0487] A PVA resin (PVA3-4) was synthesized by the same method as in Synthesis Example 3-3 using vinyl acetate, which is commonly derived from petroleum, as 100% of the raw material. The PVA had a saponification degree of 98.1 mol%, an average polymerization degree of 1,680, and an ethylene content of 4.1 mol%.

[0488] [Example 3-1]

[0489] The obtained PVA3-1 was used to prepare an aqueous emulsion by the following method, and the presence or absence of aggregates, normal-state adhesiveness, and coating properties were evaluated.

[0490] <Preparation of aqueous emulsion>

[0491] 275 g of ion exchange water was added to a 1-liter glass polymerization container equipped with a reflux condenser, a dropping funnel, a thermometer and a nitrogen blowing port, and heated to 85°C. 20.9 g of PVA-1 was dispersed and stirred for 45 minutes to dissolve. Furthermore, 0.3 g of sodium acetate was added and mixed to dissolve. Next, the aqueous solution in which the PVA-1 was dissolved was cooled and replaced with nitrogen, and then heated to 60°C while stirring at 200 rpm. After adding 2.4 g of a 20% by mass aqueous solution of tartaric acid and 3.2 g of a 5% by mass aqueous solution of hydrogen peroxide, 27 g of vinyl acetate was added to start polymerization. 30 minutes after the start of the polymerization, the initial polymerization was confirmed to be completed (the residual amount of vinyl acetate was less than 1%). After adding 1 g of a 10% by mass aqueous solution of tartaric acid and 3.2 g of a 5% by mass aqueous solution of hydrogen peroxide, 251 g of vinyl acetate was continuously added over 2 hours, and the polymerization temperature was maintained at 80°C to terminate the polymerization, thereby obtaining a polyvinyl acetate emulsion (Em-1) with a solid content concentration of 49.8% by mass.

[0492] <Amount of Aggregates Generated>

[0493] 500 g of the aqueous emulsions obtained in Examples and Reference Examples were filtered through a 60-mesh metal mesh, and the filtration residue was weighed and evaluated as follows.

[0494] A: Filtration residue is less than 1.0% by mass

[0495] B: Filtration residue is 1.0 mass % or more and less than 2.5 mass %

[0496] C: Filtration residue is 2.5% by mass or more and less than 5.0% by mass

[0497] D: Filtration residue is 5.0% by mass or more, and filtration is difficult

[0498] <Normal Adhesion>

[0499] The normal adhesiveness was evaluated in accordance with JIS K 6852 (1994).

[0500] (Bonding conditions)

[0501] Adhesive material: Hemlock / Hemlock

[0502] Coating amount: 150g / m 2 (Double-sided coating)

[0503] Pressurization conditions: 20°C, 24 hours, pressure 10kg / cm 2

[0504] (Measurement conditions)

[0505] After curing for 7 days at 20°C and 65% RH, the test pieces were subjected to a compression shear test to measure the adhesive strength (unit: kgf / cm 2 ).

[0506] <Coating properties>

[0507] 0.8 g of the aqueous emulsion was dropped onto a covering material having a width of 25 mm and a length of 20 cm, and the covering material was rubbed four times with a rubber roller and observed. The evaluation was conducted in four stages, A to D, according to the following criteria.

[0508] A: Evenly coated on the entire surface of the covering material without any agglomerates

[0509] B: Uniformly coated over 1 / 2 of the area of ​​the covering material, no aggregates are generated and the coated surface is not peeled off

[0510] C: Coating is applied to more than 1 / 2 of the area of ​​the covering material, and aggregates are formed and the coated surface peels off

[0511] D: When applied to an area less than 1 / 2 of the covering material, aggregates are formed and the coated surface peels off

[0512] [Example 3-2, Reference Examples 3-1 and 3-2]

[0513] Aqueous emulsions were prepared in the same manner as in Example 3-1 except that PVA-2, PVA-3 and PVA-4 were used instead of the copolymer 1 of Example 3-1. The amount of aggregates generated, normal adhesion and coating properties of the obtained aqueous emulsions (Em-2 to Em-4) were evaluated according to the above method, and the results obtained are summarized in Table 4.

[0514] [Table 4]

[0515]

[0516] It can be confirmed that the aqueous emulsions obtained by using the PVA of Examples 3-1 and 3-2 as a dispersion stabilizer for emulsion polymerization do not produce aggregates, and the normal adhesion is not inferior to that of Reference Examples 3-1 and 3-2, respectively, and has the same degree of adhesion. In addition, the coating property, which is an important indicator when used as an adhesive, is also sufficient, which can help save petroleum resources and inhibit global warming.

[0517] (Synthesis Example 4-2)

[0518] <Polyvinyl alcohol polymer>

[0519] 50 parts of the plant-derived vinyl acetate obtained in the above-mentioned Synthesis Example 1-1 and 50 parts of the usual petroleum-derived vinyl acetate were uniformly mixed and used as raw materials to synthesize polyvinyl acetate according to a conventional method. It was made into a methanol solution, and a saponification reaction was carried out using an alkali catalyst, and dried to obtain PVA (PVA4-1). The average polymerization degree of the PVA obtained by changing the manufacturing conditions (polymerization conditions, saponification conditions) from Synthesis Example 3-2 within the desired range was 1700, and the saponification degree was 98.5 mol%.

[0520] (Synthesis Example 4-3)

[0521] 30 parts of the plant-derived vinyl acetate obtained in Synthesis Example 1-1 and 70 parts of common petroleum-derived vinyl acetate were uniformly mixed and used as raw materials, and PVA (PVA4-2) was obtained by the same method as Synthesis Example 4-2. The average polymerization degree of this PVA was 2400 and the saponification degree was 88.0 mol%.

[0522] (Synthesis Example 4-4)

[0523] Using vinyl acetate commonly derived from petroleum as 100% of the raw material, a PVA resin pellet (PVA4-3) was synthesized by the same method as in Synthesis Example 4-2. The saponification degree of this PVA was 98.5 mol% and the average polymerization degree was 1700.

[0524] (Synthesis Example 4-5)

[0525] Using vinyl acetate commonly derived from petroleum as 100% of the raw material, a PVA resin pellet (PVA4-4) was synthesized by the same method as in Synthesis Example 4-3. The saponification degree of this PVA was 88.0 mol % and the average polymerization degree was 2400.

[0526] [Examples 4-1 and 4-2, Reference Examples 4-1 and 4-2]

[0527] The obtained PVA4-1 to PVA4-4 were subjected to a dust removal step, warm germination, germination test, accelerated aging test, and fluidity measurement by the following method to evaluate them as coating agents. The results are shown in the table.

[0528] (Processing of soybean seeds)

[0529] Seed coating compositions were prepared according to Table 5. Soybean seeds were coated with Acceleron TM Kit (Monsanto Company; contains metalaxyl, pyraclostrobin, imidacloprid and fluopyram), Color Coat Red and water base to achieve Acceleron TM The set rate is 5.8 fl.oz / cwt. 15.64 mL of slurry is applied to 2400 g of seeds.

[0530] [Table 5]

[0531]

[0532] (Dust Removal Steps)

[0533] The dried and treated soybean seeds were placed in a closed system container equipped with a filter, and stirred and vibrated under vacuum. Air was introduced into the container and discharged through the filter to filter the dust. The results of the measurement of the amount of dust on the filter are shown in Table 6 below. It can be confirmed that the amount of dust generated in the seed coating composition of Examples 4-1 and 4-2 is low and is not inferior to that of Reference Examples 4-1 and 4-2, respectively.

[0534] [Table 6]

[0535] PVA Coating composition Average weight of dust / 100,000 seeds Example 4-1 PVA 4-1 #1 0.0071 Example 4-2 PVA 4-1 #2 0.0062 Example 4-3 PVA 4-2 #1 0.0079 Reference Example 4-1 PVA 4-3 #1 0.0072 Reference Example 4-2 PVA 4-3 #2 0.0062 Reference Example 4-3 PVA 4-4 #1 0.0080

[0536] (Warm germination)

[0537] This test is used to determine the maximum germination capacity of treated and untreated seeds. Four groups of 100 seeds were prepared, planted on moist crepe cellulose paper, and placed at 25°C for 7 days. The seedlings were evaluated as "normal", "abnormal" or "dead" according to the AOSA rules (Association of Official Seed Analysts rules). The "normal" germination percentage was determined as follows: "Abnormal" or "dead" seeds were subtracted from the average number of seeds that germinated during the test period, divided by the total number of original seeds and multiplied by 100 times. The results are shown in Table 7 below. It can be confirmed that the seed coating compositions of Examples 4-1 and 4-2 do not have a harmful effect on the germination rate under ideal conditions, and are not inferior to Reference Examples 4-1 and 4-2, respectively.

[0538] [Table 7]

[0539] PVA Coating normal abnormal die Example 4-1 PVA 4-1 Coating #1 96 4 0 Example 4-2 PVA 4-1 Coating #2 95 4 1 Reference Example 4-1 PVA 4-3 Coating #1 96 4 0 Reference Example 4-2 PVA 4-3 Coating #2 95 4 1

[0540] (Low temperature germination test)

[0541] This test is designed to determine the ability of seeds to germinate under adverse conditions of high soil moisture, low soil temperature and associated microbial activity. Four groups of 100 seeds were prepared, planted on moist crepe cellulose paper and covered with sand. The covering film was placed at 10°C for 7 days, transferred to 25°C for 4 days, after which the seedlings were evaluated as "normal", "abnormal" or "dead" according to AOSA rules, taking into account vitality. The proportion of "normal" germination is determined as follows: subtract "abnormal" or "dead" seeds from the average number of seeds that germinated during the test period, divide by the total number of original seeds and multiply by 100 times. The results are shown in Table 8 below. The results of the low-temperature germination test confirmed that the normal germination rate (%) of the seed coating compositions of Examples 4-1 and 4-2 was not inferior to that of Reference Examples 4-1 and 4-2, respectively.

[0542] [Table 8]

[0543] PVA Coating normal Example 4-1 PVA 4-1 Coating #1 83 Example 4-2 PVA 4-1 Coating #2 86 Reference Example 4-1 PVA 4-3 Coating #1 83 Reference Example 4-2 PVA 4-3 Coating #2 86

[0544] (Accelerated aging test)

[0545] The seeds were weighed, placed in a water-jacketed chamber, and maintained at 43°C and high humidity for 72 hours. Four groups of 100 seeds were prepared, planted on moist crepe cellulose paper, and covered with sand. The planted covering film was placed at 25°C for 7 days, after which normal seedlings were evaluated according to AOSA rules. The "normal" germination percentage was determined as follows: any "abnormal" or "dead" seeds were subtracted from the average number of seeds that germinated during the test period, divided by the total number of original seeds and multiplied by 100 times. The results are shown in Table 9 below. It can be confirmed that the seed coating compositions of Examples 4-1 and 4-2 do not reduce germination and are not inferior to Reference Examples 4-1 and 4-2, respectively.

[0546] [Table 9]

[0547] PVA Coating normal Example 4-1 PVA 4-1 Coating #1 71 Example 4-2 PVA 4-1 Coating #2 78 Reference Example 4-1 PVA 4-3 Coating #1 71 Reference Example 4-2 PVA 4-3 Coating #2 78

[0548] (Fluid Flowability)

[0549] The dry flow of soybeans was measured as the time required for 1200 g of seeds (4 groups of 300 g) to flow through a funnel at a relative humidity of 56% and 25°C. The addition of coating to soybeans tends to greatly slow down the flow of seeds, which is not a desirable characteristic. As shown in Table 9, it can be confirmed that when the seed coating composition of the present invention is used, the seeds of Reference Examples 4-1 and 4-2 flow effectively and quickly to the same extent, and are not inferior.

[0550] Seed bridging occurs when seeds coming out of the coating machine are collected in the storage hopper and compressed by the seeds facing each other. This leads to problems in seed treatment facilities from the perspectives of machine short circuit, labor and time. As shown in Table 10, it can be confirmed that when the seed coating composition of the present invention is used, there is no tendency of bridging, which is not inferior to Reference Examples 4-1 and 4-2.

[0551] [Table 10]

[0552]

[0553] (Synthesis example 5-2)

[0554] <Dispersion Stabilizer for Suspension Polymerization>

[0555] 50 parts of the plant-derived vinyl acetate obtained in the above-mentioned Synthesis Example 1-1 and 50 parts of the common petroleum-derived vinyl acetate were uniformly mixed and used as raw materials, and acetaldehyde was used as a chain transfer agent to synthesize polyvinyl acetate according to a conventional method. This was made into a methanol solution, and a saponification reaction was carried out using an alkali catalyst, and dried to obtain PVA (PVA5-1). The average polymerization degree of this PVA was 750, and the saponification degree was 72.0 mol%.

[0556] (Synthesis Example 5-3)

[0557] 50 parts of the plant-derived vinyl acetate obtained in the above-mentioned Synthesis Example 1-1 and 50 parts of the usual petroleum-derived vinyl acetate were uniformly mixed and used as raw materials to synthesize polyvinyl acetate according to a conventional method. It was made into a methanol solution, saponified using an alkali catalyst, and dried to obtain PVA (PVA5-2). The average polymerization degree of the PVA obtained by changing the manufacturing conditions (polymerization conditions, saponification conditions) from Synthesis Example 3-2 within the desired range was 2400, and the saponification degree was 80.0 mol%.

[0558] (Synthesis Example 5-4)

[0559] Using vinyl acetate, which is commonly derived from petroleum, as 100% of the raw material, PVA (PVA5-3) was synthesized by the same method as in Synthesis Example 5-2. The average polymerization degree of this PVA was 750, and the saponification degree was 72.0 mol%.

[0560] (Synthesis Example 5-5)

[0561] Using vinyl acetate, which is commonly derived from petroleum, as 100% of the raw material, PVA (PVA5-4) was synthesized by the same method as in Synthesis Example 5-3. The average polymerization degree of this PVA was 2400, and the saponification degree was 80.0 mol%.

[0562] [Table 11]

[0563]

[0564] [Examples 5-1 and 5-2, Reference Examples 5-1 and 5-2]

[0565] The obtained PVA5-1 to PVA5-4 were subjected to suspension polymerization of vinyl chloride by the following method. Then, the average particle size, the amount of coarse particles, and the plasticizer absorption of the obtained vinyl chloride polymer particles were evaluated. The evaluation results are shown in Table 12.

[0566] (Suspension Polymerization of Vinyl Chloride)

[0567] The vinyl alcohol copolymer obtained above is dissolved in deionized water in an amount equivalent to 800 ppm relative to vinyl chloride to prepare a dispersion stabilizer aqueous solution. 1150 g of the dispersion stabilizer aqueous solution obtained in this way is put into a 5 L autoclave. Next, 1.5 g of a 70% toluene solution of diisopropyl peroxydicarbonate is put into the autoclave. Degas until the pressure in the autoclave reaches 0.0067 MPa to remove oxygen. Thereafter, 1000 g of vinyl chloride is put in, the temperature of the contents in the autoclave is raised to 57°C, and polymerization is started under stirring. The pressure in the autoclave at the start of polymerization is 0.83 MPa. After 7 hours from the start of polymerization, the polymerization is stopped when the pressure in the autoclave reaches 0.44 MPa, and the unreacted vinyl chloride is removed. Thereafter, the polymerization slurry is taken out and dried overnight at 65°C to obtain vinyl chloride polymer particles.

[0568] (Evaluation of vinyl chloride polymer particles)

[0569] (1) Average particle size of vinyl chloride polymer particles

[0570] The particle size distribution was determined by dry sieve analysis using a metal mesh based on the Taylor standard sieve number. The results were plotted in the Rosin-Rammler distribution and the average particle size (d p50 ; median particle size).

[0571] (2) Amount of coarse particles of vinyl chloride polymer particles

[0572] The content of the residue on the JIS standard 42 mesh sieve is expressed in mass %. The smaller the number, the less coarse particles there are and the better the polymerization stability.

[0573] (3) Plasticizer absorption (CPA)

[0574] The mass of a 5 mL syringe containing 0.02 g of absorbent cotton was measured (denoted as A (g)), 0.5 g of vinyl chloride polymer particles were added thereto and the mass was measured (denoted as B (g)), 1 g of dioctyl phthalate (DOP) was added thereto, and after standing for 15 minutes, the mixture was centrifuged at 3000 rpm for 40 minutes and the mass was measured (denoted as C (g)). The plasticizer absorbency (%) was calculated according to the following formula.

[0575] Plasticizer absorption (%) = 100 × [{(CA) / (BA)}-1]

[0576] [Table 12]

[0577] PVA Average particle size (μm) Amount of coarse particles (%) Plasticizer absorption (%) Example 5-1 PVA 5-1 155 0.5 26.0 Example 5-2 PVA 5-2 140 0.2 15.0 Reference Example 5-1 PVA 5-3 156 0.6 25.9 Reference Example 5-2 PVA 5-4 141 0.2 14.8

[0578] It can be confirmed that the average particle size, coarse particle amount, and plasticizer absorption of the vinyl chloride polymer particles of the PVA resin of Examples 5-1 and 5-2 are not inferior to those of Reference Examples 5-1 and 5-2, respectively, and have the same performance as a dispersion stabilizer for suspension polymerization. In addition, it can contribute to saving petroleum resources and inhibiting global warming.

[0579] (Synthesis Example 6-2)

[0580] <Dispersion Stabilizing Agent for Suspension Polymerization>

[0581] 50 parts of the plant-derived vinyl acetate obtained in the above-mentioned Synthesis Example 1-1 and 50 parts of the usual petroleum-derived vinyl acetate were uniformly mixed and used as raw materials, and polyvinyl acetate was synthesized according to a conventional method. It was made into a methanol solution, and a saponification reaction was carried out using an alkali catalyst, and dried to obtain PVA (PVA6-1). The average polymerization degree of the PVA obtained by changing the manufacturing conditions (polymerization conditions, saponification conditions) from Synthesis Example 3-2 within the desired range was 300, and the saponification degree was 55.0 mol%.

[0582] (Synthesis Example 6-3)

[0583] 50 parts of the plant-derived vinyl acetate obtained in the above-mentioned Synthesis Example 1-1 and 50 parts of the usual petroleum-derived vinyl acetate were uniformly mixed and used as raw materials, and 3-mercaptopropionic acid (3-MPA) was used as a chain transfer agent to synthesize polyvinyl acetate according to a conventional method. It was made into a methanol solution, and a saponification reaction was carried out using an alkali catalyst, and dried to obtain PVA (PVA6-2). The average polymerization degree of this PVA was 500, and the saponification degree was 40.0 mol%.

[0584] (Synthesis Example 6-4)

[0585] A PVA resin (PVA6-3) was synthesized by the same method as in Synthesis Example 6-2 using vinyl acetate, which is commonly derived from petroleum, as 100% of the raw material. The average polymerization degree of this PVA was 300, and the saponification degree was 55.0 mol%.

[0586] (Synthesis Example 6-5)

[0587] Using vinyl acetate, which is commonly derived from petroleum, as 100% of the raw material, a PVA resin pellet (PVA6-4) was synthesized by the same method as in Synthesis Example 6-3. The average polymerization degree of this PVA was 500, and the saponification degree was 40.0 mol%.

[0588] (Synthesis Example 6-6)

[0589] <Dispersion Stabilizer for Suspension Polymerization>

[0590] Polyvinyl acetate was synthesized by a conventional method using vinyl acetate, which is usually derived from petroleum, as 100% of the raw material. It was made into a methanol solution, and a saponification reaction was carried out using an alkali catalyst, and dried to obtain PVA (PVA6-5). The average polymerization degree of this PVA was 2000, and the saponification degree was 80 mol%.

[0591] [Table 13]

[0592]

[0593] [Examples 6-1 and 6-2, Reference Examples 6-1 and 6-2]

[0594] The obtained PVA6-1 to PVA6-4 were subjected to suspension polymerization of vinyl chloride by the following method. Then, the obtained vinyl chloride polymer particles were evaluated for (1) average particle size, (2) plasticizer absorption, (3) monomer removal property, and (4) fisheye. The evaluation results are shown in Table 14.

[0595] [Preparation Example 1 of Aqueous Solution of Dispersion Stabilizing Aid for Suspension Polymerization]

[0596] PVA, methanol and distilled water were mixed so that the concentration of PVA6-1 or PVA6-3 described in Table 13 was 40 mass % and the concentration of methanol was 5 mass %, and stirred at room temperature for 2 hours using a magnetic stirrer to obtain an aqueous solution of a dispersion stabilizing agent for suspension polymerization.

[0597] [Preparation Example 2 of Aqueous Solution of Dispersion Stabilizing Aid for Suspension Polymerization]

[0598] PVA6-2 and PVA6-4 described in Table 13 were mixed with distilled water at a concentration of 5 mass %, and stirred at room temperature for 2 hours using a magnetic stirrer to obtain an aqueous solution of a dispersion stabilizing agent for suspension polymerization.

[0599] (Suspension Polymerization of Vinyl Chloride)

[0600] A dispersion stabilizer for suspension polymerization (PVA6-5) having a viscosity average polymerization degree of 2000 and a saponification degree of 80 mol% was added to a 5L autoclave in the form of 100 parts of deionized water solution in a manner that the concentration was 1000 ppm relative to the vinyl chloride monomer. The dispersion stabilizer aqueous solution obtained in the above-mentioned Preparation Example 1 was added in a manner that the concentration of PVA6-1 in the dispersion stabilizer aqueous solution was 200 ppm relative to the vinyl chloride monomer. Deionized water was added in a manner that the total amount of deionized water added was 1640 parts. Next, 1.07 parts of a 70% toluene solution of di(2-ethylhexyl) peroxydicarbonate was added to the autoclave. After nitrogen was introduced 5 times in a manner that the pressure in the autoclave was 0.2 MPa, the introduced nitrogen was purged, and after the autoclave was fully replaced with nitrogen to remove oxygen, 940 parts of vinyl chloride were added, the contents in the autoclave were heated to 65°C, and the polymerization of the vinyl chloride monomer was started under stirring. The pressure in the autoclave at the start of polymerization was 1.05 MPa. About 3 hours after the start of polymerization, the polymerization was stopped when the pressure in the autoclave reached 0.70 MPa, and the unreacted vinyl chloride monomer was removed. The polymerized product was taken out and dried at 65° C. for 16 hours to obtain vinyl chloride polymer particles.

[0601] (Evaluation of vinyl chloride polymer particles)

[0602] (1) Average particle size of vinyl chloride polymer particles

[0603] The particle size distribution was determined by dry sieve analysis using a metal mesh based on the Taylor standard sieve number. The results were plotted in the Rosin-Rammler distribution and the average particle size (d p50 ; median particle size).

[0604] (2) Plasticizer absorption

[0605] The mass of a 5 mL syringe containing 0.02 g of absorbent cotton was measured (denoted as A (g)), 0.5 g of vinyl chloride polymer particles were added thereto and the mass was measured (denoted as B (g)), 1 g of dioctyl phthalate (DOP) was added thereto, and after standing for 15 minutes, the mixture was centrifuged at 3000 rpm for 40 minutes and the mass was measured (denoted as C (g)). The plasticizer absorbency (%) was calculated according to the following formula.

[0606] Plasticizer absorption (%) = 100 × [{(CA) / (BA)}-1]

[0607] (3) Demonomerization (ratio of residual monomer)

[0608] The polymerization product of the suspension polymerization of vinyl chloride was taken out and dried at 75° C. for 1 hour and 3 hours, and the amount of residual monomers at each time point was measured by headspace gas chromatography. The residual monomer ratio was calculated by the following formula.

[0609] Residual monomer ratio = (residual monomer amount at 3 hours of drying / residual monomer amount at 1 hour of drying) × 100

[0610] The smaller the value is, the greater the proportion of monomers remaining in the vinyl chloride polymer particles removed by drying from 1 hour to 3 hours, i.e., within 2 hours. This value becomes an indicator of the degree of removal of residual monomers, i.e., the monomer removal property.

[0611] (4) Determination of fish eyes

[0612] Using a roll mixer, 100 parts of the obtained vinyl chloride polymer particles, 35 parts of DOP (dioctyl phthalate), 5 parts of tribasic lead sulfate and 1 part of zinc stearate were mixed at 150°C for 7 minutes to prepare a 0.1 mm thick sheet, and the number of fish eyes per 100 mm×100 mm of the sheet was measured.

[0613] [Table 14]

[0614]

[0615] It can be confirmed that the average particle size, plasticizer absorption, monomer removal and fisheye value of the vinyl chloride polymer particles of the PVA resin of Examples 6-1 and 6-2 are not inferior to those of Reference Examples 6-1 and 6-2, respectively, and have the same performance as a dispersion stabilization aid for suspension polymerization. In addition, it can contribute to saving petroleum resources and inhibiting global warming.

[0616] (Synthesis Example 7-2)

[0617] 50 parts of the plant-derived vinyl acetate obtained in the above-mentioned Synthesis Example 1-1 and 50 parts of the usual petroleum-derived vinyl acetate were uniformly mixed and used as raw materials, and polyvinyl acetate was synthesized according to a conventional method. It was made into a methanol solution, and a saponification reaction was carried out using an alkali catalyst, and dried to obtain PVA (PVA7-1). The average polymerization degree of the PVA obtained by changing the manufacturing conditions (saponification conditions) from Synthesis Example 3-2 within the desired range was 1,750, and the saponification degree was 98.5 mol%.

[0618] (Synthesis Example 7-3)

[0619] PVA (PVA7-2) was obtained by the same method as Synthesis Example 7-2 except that 30 parts of plant-derived vinyl acetate obtained in Synthesis Example 1-1 and 70 parts of common petroleum-derived vinyl acetate were uniformly mixed and used as raw materials, and common petroleum-derived ethylene was copolymerized. The average polymerization degree of this PVA was 1,720, the saponification degree was 97.5 mol%, and the content of ethylene units was 4.2 mol%.

[0620] (Synthesis Example 7-4)

[0621] A PVA resin (PVA7-3) was synthesized by the same method as in Synthesis Example 7-2 using vinyl acetate commonly derived from petroleum as 100% of the raw material. The saponification degree of this PVA was 98.7 mol % and the average degree of polymerization was 1,780.

[0622] (Synthesis Example 7-5)

[0623] A PVA resin (PVA7-4) was synthesized by the same method as in Synthesis Example 7-3 using vinyl acetate, which is commonly derived from petroleum, as 100% of the raw material. The PVA had a saponification degree of 98.1 mol%, an average polymerization degree of 1,680, and an ethylene content of 4.1 mol%.

[0624] (Oxygen barrier)

[0625] The multilayer structures obtained in the examples and comparative examples were conditioned at 20°C and 85% RH for 5 days, and then the oxygen permeability (cc / m 2 ·day·atm).

[0626] Temperature: 20℃

[0627] Humidity on oxygen supply side: 85% RH

[0628] Humidity of carrier gas side: 85% RH

[0629] Carrier gas flow rate: 10mL / min

[0630] Oxygen pressure: 1.0atm

[0631] Carrier gas pressure: 1.0atm

[0632] [Example 7-1]

[0633] (Manufacturing of Multilayer Structure)

[0634] A multilayer structure was produced by the following method for the obtained PVA7-1, and the oxygen barrier property (oxygen permeability) was evaluated.

[0635] 100 parts by weight of the obtained vinyl alcohol polymer is added to water to prepare an aqueous solution (coating agent) having a concentration of 7% by weight of the vinyl alcohol polymer, and then the solution is allowed to stand at 20°C and 60% RH for 1 hour. An anchor coating agent (adhesive) is applied to layer (D) of a stretched polyethylene terephthalate (OPET) film (substrate) having a thickness of 15 μm to form an adhesive component layer on the surface of the OPET film. Using a gravure coater, the coating agent obtained above is applied to the surface of the adhesive component layer at 40°C, and then dried at 120°C to form a layer (C). In order to promote the reaction of the anchor coating agent, the film is further heat-treated at 160°C for 120 seconds to obtain a multilayer structure. The thickness of layer (C) is 2 μm. The oxygen permeability of the obtained multilayer structure is shown in Table 15.

[0636] [Example 7-2, Reference Examples 7-1 and 7-2]

[0637] The multilayer structure was produced in the same manner as in Example 7-1 except that PVA7-2, PVA7-3 and PVA7-4 were used instead of PVA7-1. The oxygen permeability of the obtained multilayer structure was evaluated in accordance with the above method and the results are summarized in Table 4.

[0638] [Table 15]

[0639]

[0640] It can be confirmed that the oxygen barrier properties of the multilayer structures containing PVA of Examples 7-1 and 7-2 are not inferior to those of Reference Examples 7-1 and 7-2, respectively, and have the same degree of barrier properties. The multilayer structure of the present invention and the packaging material having the same have excellent oxygen barrier properties and can contribute to saving petroleum resources and suppressing global warming.

[0641] (Synthesis example 8-2)

[0642] 50 parts of the plant-derived vinyl acetate obtained in the above-mentioned Synthesis Example 1-1 and 50 parts of the usual petroleum-derived vinyl acetate were uniformly mixed and used as raw materials to synthesize polyvinyl acetate according to a conventional method. It was made into a methanol solution, and a saponification reaction was carried out using an alkali catalyst, and dried to obtain PVA (PVA8-1). The average polymerization degree of the PVA obtained by changing the manufacturing conditions (saponification conditions) from Synthesis Example 3-2 within the desired range was 1,750, and the saponification degree was 98.5 mol%.

[0643] (Synthesis Example 8-3)

[0644] PVA (PVA8-2) was obtained by the same method as Synthesis Example 8-2 except that 30 parts of plant-derived vinyl acetate obtained in Synthesis Example 1-1 and 70 parts of common petroleum-derived vinyl acetate were uniformly mixed and used as raw materials, and common petroleum-derived ethylene was copolymerized. The average polymerization degree of this PVA was 1,720, the saponification degree was 97.5 mol%, and the content of ethylene units was 4.2 mol%.

[0645] A PVA resin (PVA8-3) was synthesized by the same method as in Synthesis Example 8-2 using vinyl acetate commonly derived from petroleum as 100% of the raw material. The saponification degree of this PVA was 98.7 mol % and the average degree of polymerization was 1,780.

[0646] (Synthesis Example 8-5)

[0647] A PVA resin (PVA8-4) was synthesized by the same method as in Synthesis Example 8-3 using vinyl acetate, which is commonly derived from petroleum, as 100% of the raw material. The PVA had a saponification degree of 98.1 mol%, an average polymerization degree of 1,680, and an ethylene unit content of 4.1 mol%.

[0648] [Examples 8-1 and 8-2, Reference Examples 8-1 and 8-2]

[0649] The obtained PVA8-1 to PVA8-4 were heated and dissolved in hot water at 95°C for 2 hours to prepare a coating agent having a solid content concentration of 6%. The coating agent was evaluated by the following method. The results are shown in Table 16.

[0650] [Test of using coating agent to produce coated paper]

[0651] The coating agent was applied manually as a coating liquid on a glass paper having a basis weight of 64 gsm at 20° C. using a wire rod. Next, the coating agent was dried at 105° C. for 1 minute using a drum-type rotary dryer. The coating amount calculated as the solid content of the coating agent was 1.0 gsm (single side). The obtained coated paper was humidified at 20° C. and 65% RH for 72 hours, and the physical properties of the coated paper were measured.

[0652] [Water resistance test of coated paper]

[0653] About 0.1 g of ion exchange water at 20° C. was dropped onto the surface of the coated paper produced by the above method (coating surface), and then rubbed with fingertips to observe the dissolution state of the coating agent and evaluate according to the following criteria.

[0654] 0-Excellent water resistance, no slipping feeling.

[0655] △ - A portion of the coating agent was emulsified.

[0656] × - The coating agent is dissolved.

[0657] [Evaluation for release paper applications: Air permeability resistance measurement]

[0658] According to JIS P 8117:2009, the air permeability resistance of the coated paper was measured using a Wangyan smoothness air permeability tester.

[0659] [Evaluation for release paper applications: Toluene barrier test]

[0660] After applying (5×5 cm) colored toluene (red) in which red food red was dissolved on the coated surface of the coated paper, the degree of print-through (small red spots and / or coloration of the entire coated surface) to the back side (uncoated surface) was evaluated according to the following criteria.

[0661] 5-No spots on the back

[0662] 4-Produce (1, 2) spots

[0663] 3- A large number of spots are produced (about 10-20% of the toluene coated surface)

[0664] 2- Approximately 50% of the coated surface is colored

[0665] 1- Overall coloring of the coated surface

[0666] [Evaluation for oil-resistant paper applications: KIT test, folding KIT test]

[0667] According to TAPPINo.T559cm-02, the KIT test of the flat surface and the bent part of the coating surface is carried out. Evaluation is performed by visual inspection. It should be noted that the KIT value of commercially available oil-resistant paper using fluororesin is usually above grade 5, and the oil resistance that does not become a problem in general use is above grade 5. Therefore, the oil resistance of the coated paper is preferably above grade 5, and in applications requiring higher oil resistance, it is preferably above grade 7, and more preferably above grade 10.

[0668] In the KIT test of the bent portion, the coated paper was placed in a manner such that the coated surface became the outer surface, and the bent portion was tested from above at a width of 1.0 mm, a depth of 0.7 mm, and a pressure of 2.5 kgf / cm 2 The coated paper was then unfolded and the oil resistance of the folded portion was measured using TAPPINo.T559cm-02. The measurement was performed visually.

[0669] [Table 16]

[0670]

[0671] It can be confirmed that the physical properties of the coated paper of the coating agent containing PVA of Examples 8-1 and 8-2 are not inferior to those of Reference Examples 8-1 and 8-2, respectively, and have the same degree of performance. The paper coating agent of the present invention and the paper coated therewith have excellent barrier properties and oil resistance, and can contribute to saving petroleum resources and inhibiting global warming.

Claims

1. A vinyl alcohol polymer (X) obtained by polymerizing a plant-derived vinyl ester monomer (A) and a petroleum-derived vinyl ester monomer (B) and saponifying the polymer, wherein the molar ratio of (A) / (B) is 5 / 95 to 90 / 10. 2 . The vinyl alcohol polymer (X) according to claim 1 , further comprising ethylene units, wherein the content of the ethylene units is 1 mol % or more and less than 20 mol %.

3. A slurry additive comprising the vinyl alcohol polymer (X) according to claim 1 or 2.

4. Drilling mud comprising the slurry additive according to claim 3.

5. The drilling mud according to claim 4, further comprising water and bentonite.

6. Cement slurry comprising the slurry additive according to claim 3.

7. The cement slurry according to claim 6, further comprising a liquid agent and a curable powder.

8. A filler for underground treatment, comprising the vinyl alcohol polymer (X) according to claim 1 or 2.

9. The underground treatment filler according to claim 8, wherein: The vinyl alcohol polymer (X) contains other unsaturated monomers (C) copolymerizable with the vinyl ester monomer.

10. The filling material for underground treatment according to claim 8 or 9, further comprising a plasticizer.

11. A multilayer structure comprising: a layer (C) containing the vinyl alcohol polymer (X) according to claim 1 or 2 and a layer (D) containing a resin, The resin is at least one resin selected from polyolefin resin, polyester resin, polyamide resin, polyvinyl chloride (PVC) resin, ABS resin, polylactic acid (PLA) resin, polybutylene succinate (PBS) resin, polyhydroxyalkanoate (PHA) resin, polyhydroxybutyrate / hydroxyhexanoate (PHBH) resin, starch and cellulose.

12. The method for producing a multilayer structure according to claim 11, comprising: a step of preparing an aqueous solution containing the vinyl alcohol polymer (X) to obtain a coating agent; and A step of applying the coating agent to the surface of a substrate containing a resin, The resin is at least one resin selected from polyolefin resin, polyester resin, polyamide resin, polyvinyl chloride (PVC) resin, ABS resin, polylactic acid (PLA) resin, polybutylene succinate (PBS) resin, polyhydroxyalkanoate (PHA) resin, polyhydroxybutyrate / hydroxyhexanoate (PHBH) resin, starch and cellulose.

13. A packaging material comprising the multilayer structure according to claim 11.

14. A paper coating agent comprising the vinyl alcohol polymer (X) according to claim 1 or 2.

15. Coated paper, which is obtained by coating the paper coating agent according to claim 14 on paper. The coated paper according to claim 15 , which is a release paper base paper.

17. The coated paper according to claim 15, which is oil-resistant paper.

18. A seed coating composition comprising the vinyl alcohol polymer (X) according to claim 1 or 2. The seed coating composition according to claim 18 , further comprising one or more hydrophobic pesticides.

20. An aqueous emulsion comprising a dispersant and a dispersoid, The dispersoid comprises a polymer (Y1) containing ethylenically unsaturated monomer units, The dispersant comprises the vinyl alcohol polymer (X) according to claim 1 or 2.

21. The aqueous emulsion according to claim 20, wherein The polymer (Y1) containing ethylenically unsaturated monomer units is a polymer having specific units derived from at least one selected from vinyl ester monomers, (meth)acrylate monomers, styrene monomers and diene monomers, and the content of the above units in the polymer relative to all monomer units is 70% by mass or more.

22. The aqueous emulsion according to claim 20 or 21, further comprising a polyisocyanate compound.

23. An adhesive comprising the aqueous emulsion according to any one of claims 20 to 22.

24. A dispersion stabilizer for suspension polymerization of a vinyl compound, comprising the vinyl alcohol polymer (X) according to claim 1 or 2.

25. A method for producing a vinyl resin, comprising: A step of performing suspension polymerization of a vinyl compound in the presence of the dispersion stabilizer for suspension polymerization according to claim 24.

26. The method for producing a vinyl resin according to claim 25, comprising: A step of performing suspension polymerization of a vinyl compound in the presence of the above-mentioned dispersion stabilizer for suspension polymerization and a further dispersion stabilization auxiliary agent, The dispersion stabilization aid includes a vinyl alcohol polymer (Y2) having a saponification degree of less than 65 mol %.

27. A dispersion stabilizing agent for suspension polymerization of a vinyl compound, comprising the vinyl alcohol polymer (X) according to claim 1 or 2, The saponification degree of the vinyl alcohol polymer (X) is 20 mol% or more and less than 60 mol%.

28. A method for producing a vinyl resin, comprising: A step of performing suspension polymerization of a vinyl compound in the presence of the dispersion stabilization aid for suspension polymerization and the dispersion stabilizer for suspension polymerization according to claim 27, The dispersion stabilizer for suspension polymerization contains a vinyl alcohol polymer (Y3) having a saponification degree of 65 mol % or more and a viscosity average polymerization degree of 600 or more.

29. The method for producing a vinyl resin according to claim 28, wherein The mass ratio of the dispersion stabilizer to the dispersion stabilization aid (dispersion stabilizer / dispersion stabilization aid) is 95 / 5 to 20 / 80.

Citation Information

Patent Citations

  • Dispersion stabilizer for suspension polymerization of vinyl compound

    JP1993088251B2

  • Dispersant aid for suspension polymerization of vinyl compound

    JP1997100301A

  • Dispersion assistant for suspension polymerization of vinyl-based compound

    JP1998147604A

  • Polyvinyl alcohol polymer

    JP1998168128A

  • Aqueous solution of partially saponified vinyl ester-based resin excellent in stability

    JP1998259213A